Hydrological dynamics regulate reactive oxygen species production in the largest freshwater lake of China - Wenkang Li; Siwen Li; Dinggui Wu; Chaoran Guo; Huacheng Xu; Na Song (Water Research, 2026)

A Multi-Index decision framework of optimal gasket selection for tunnel segmental joints: Integrating variable weight and extension cloud model - Huai-Na Wu; Hua-Yong Li; De-Sai Guo; Yu Li; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2026)

Digital model reconstruction of shield tunnels based on 3D point cloud - Yu Li; Huai-Na Wu; Dong-Lin Feng; Si-Qi Yang; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2026)

Genome-wide screening and functional analysis of protein glycosylation-related genes involved in tomato fruit ripening - Bowen Li; Ye Liu; Peiwen Wu; Zheng Bian; Cailian Wang; Chunyang Wang; Na Ren; Yangyang Han; Benzhong Zhu (Plant Science, 2026)

Roasting-induced hazardous aldehydes in nuts: Systematic profiling, formation dynamics, and food safety implications - Zhiyuan Ning; Jie Han; Na Li; Xue Li; Xiaolan Hu; Jian-Lin Wu (Food Control, 2026)

Molecular insights into the formation of heterogeneous polyamide reverse osmosis membranes during interfacial polymerization - Na Li; Zhiying Wu; Lei Qi; Yujian Yao; Xuan Zhang (Desalination, 2026)

IGFL2-AS1 is associated with poor prognosis in cervical cancer and promotes disease progression via the miR-126-5p/MACC1 axis - Zhibing Wu; Donglian Lan; Chao He; Na Li (Molecular Biology Reports, 2026)

Two-stage instance segmentation method based on Tunnel-SPVNet for shield tunnel segments - Yu Li; Huai-Na Wu; Dong-Lin Feng; Yu-Liang Li; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2026)

Enhancement mechanism of tunnel linings strengthened with sprayed ultra-high-performance concrete: Full-scale experiment and simulation - Tao Chen; Huai-Na Wu; Yu Li; Si-Qi Yang; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2026)

Neurotoxicity and mechanisms of deltamethrin and its metabolite 3-PBA in HT22 cells - Yihui Liang; Tianli Shi; Ruike Zhang; Guanghua Mao; Weiwei Feng; Qian Li; Yao Chen; Na Chen; Xiangyang Wu (Toxicology, 2026)

XsiAMT1.1a was identified as a novel ammonium uptake functional gene and its overexpression combined with GA4 application significantly increased yield in Arabidopsis thaliana - Xiao Han; Zhao-Hua Gong; Jie Cao; Li-Na Ye; Yuan Cheng; Yu-Xuan Du; Ting-Ting Zhao; Hai-Long Wu; Chang Zhang (Plant Science, 2026)

Targeted regulation and extraction mechanism of rare earth elements and thorium during the decomposition of rare earth concentrates - Xiaowei Zhang; Likai Zang; Feng Guo; Yanhong Hu; Jinxiu Wu; Wenjun Fan; Jianguo Cui; Na Li; Xiaodong Wang; Ruifeng Ma (Minerals Engineering, 2026)

Columnar optical properties of locally emitted light-absorbing carbonaceous aerosols - Kang Hu; Hong Liao; Dantong Liu; Jianbing Jin; Siyuan Li; Yangzhou Wu; Yuxing Gao; Xiaotong Jiang; Shitong Zhao; Ping Tian; Fei Wang; Na Kang; et al. (Journal of Environmental Sciences, 2026)

A SIRIUS-Guided Integrative Modificomics and Oligosaccharidomics (SGIMO) strategy unveils bioactive modified metabolites in Chinese rice wine - Chengfeng Gao; Shuxian Yang; Wen Miao; Pingping Dong; Jian-Lin Wu; Na Li (Food Research International, 2026)

Microalgae-based bioremediation of reverse osmosis concentrate (ROC): Mechanisms, techno-economic bottlenecks, and circular bioeconomy perspectives - Na-Hui Hao; Jun Li; Ya-Rong Qi; Zhuo Chen; Yu-Ming Wang; Yu-Jia Gao; Xu-Cheng Cai; Yu Hong; Hong-Ying Hu; Yin-Hu Wu (Desalination, 2026)

CAMERA: A programmable CRISPR-gated logic system for high-fidelity assessment of Mycobacterium tuberculosis - Jiu Pu; Dan Bai; Yaoyi Zhang; Yiqi Zhang; Li Zhang; Yu He; You Wu; Na Yin; Zhe He; Shun Yao; Ting Xu; Yongchang Wu; et al. (Chemical Engineering Journal, 2026)

Fe3O4 supported on rabbit-tail grass-derived biochar for energy-efficient CO2 desorption: Synergistic effects of acid sites and carbon-assisted electron-driving mechanism - Lianming Wu; Anqi Jia; Xingyong Li; Senshen Yu; Xuexiang Fu; Na Liu; Yubao Chen (Biomass and Bioenergy, 2026)

An ER-targeted electronic-switched cascade probe for synchronous dual-channel imaging of H2S and HClO during liver fibrosis - Jiaxue Yang; Yi Le; Na Wang; Beibei Wu; Yuyang Song; Ting Wang; Birong Yang; Fan Zhou; Li Liu (Analytica Chimica Acta, 2026)

SNSTFM: A novel data fusion approach based on spatial non-stationarity to generate fine-resolution land surface temperature - Laifu Zhang; Na Li; Sensen Wu; Haoyu Jing; Jihan Wang; Fanen Meng; Yiming Yan; Huanfeng Shen; Bo Huang; Zhenhong Du (Remote Sensing of Environment, 2026)

The underappreciated diversity of functional pigments in red yeast rice revealed by an integrated multi-engine mining strategy (IMMS) - Yujuan Ban; Wen Miao; Xinyang Jin; Siyuan Chen; Xiaoer Lou; Jian-Lin Wu; Na Li (Food Chemistry, 2026)

Amino-engineered interfacial photocatalytic membrane with enhanced antifouling and self-cleaning performance for sustainable water purification - Qiaozhi Wang; Qi Zhang; Na Qi; Yehao Yan; Yan Zhang; Ensheng Xu; Hong Chen; Ziyi Wu; Zehui Zhao; Dan Huang; Qingwang Xue; Ying Li; et al. (Chemical Engineering Journal, 2026)

A heparan-like glycosaminoglycan from the white jade snail: Precise structural elucidation, alkaline-induced artificial changes, and non-anticoagulant heparanase inhibition - Pin Wang; Na Gao; Qijiang Mao; Lutan Zhou; Yu Wang; Ying Pan; Fengyun Wu; Penghao Kang; Zanyang Min; Yujun Ma; Huifang Sun; Xiang Shi; et al. (Carbohydrate Polymers, 2026)

GLSP ameliorates monocrotaline-induced pulmonary arterial hypertension through inhibition of the PI3K/AKT and MAPK signaling pathways - Yingying Wei; Siying Zuo; Na Deng; Haijun Guo; Liwei You; Yaping Zuo; Yan Wu; Zhangrong Chen; Wei Li; Xiaoyun Si (Journal of Molecular Histology, 2026)

Mapping the True 3D Architecture: Quantitative Morphological Diversity of Human Hepatic Functional Unit Revealed by Fluorescence Micro-optical Section Tomography - Na Chen; Hongjun Liu; Xiaofeng Mei; Silin Liu; Hongjia Hu; Yunxi Lv; Qi Li; Wei Feng; Yifang Ping; Lu Zheng; Shiwu Dong; Yi Wu (Tissue and Cell, 2026)

Investigation on performance-based deformation control criteria for shield tunnel linings under typical adjacent construction disturbances - Dong-Lin Feng; Yu Li; Huai-Na Wu; Si-Qi Yang; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2026)

Phenylbutene dimers and saturated phenylbutene derivatives from Zingiber montanum with anti-inflammatory potential - Zhi-hang Wu; Lu Chen; Jin-na Zhao; Lv-you Wan; Fa-xiang Guo; Lei Zhang; Li-bo Wang; Jin-hui Wang; Xian-mei Piao (Phytochemistry, 2026)

Green synchronous fluorescence spectroscopy using non-carcinogenic standard: Rapid determination of carcinogenic polycyclic aromatic hydrocarbons in dairy products - Yi-Han Guo; Jia-Rong He; Jia-Wen Wei; Hong-Jun Liu; Jia-Lin Li; Ping-Ping Wu; Gaofeng Zheng; He-Dong Luo; Na Li; Yao-Qun Li (Food Control, 2026)

Polystyrene microplastic exposure induces hepatic damage via immune-modulated autophagy and ferroptosis in Nile tilapia (Oreochromis niloticus) - Feilong Wang; Xiaolong Fan; Xiaomeng Guo; Na Guo; Tian Gao; Changle Zhao; Yuanyuan Li; Haiyan Xu; Fan Bai; Yixin Chen; Deshou Wang; Lina Sun; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Enhanced hydrothermal stability of Cu-SSZ-13 zeolite catalyst in NH3-SCR via surface-deposited CeO2 nanoparticles - Hui Wu; Na Zhao; Jiarong Li; Yu Wang; Aiping Jia; Ji-Qing Lu (Chemical Engineering Journal, 2026)

Mango peel pectin as a high-ester emulsifier for carotenoid delivery: Structural characterization and application in low-fat ice cream - Teng-Gen Hu; Huan Zhang; Lu Li; Yu-Qing Hu; Jing Wen; Bo Zou; Jian Peng; Li-Na Cheng; Ji-Jun Wu; Geng-Sheng Xiao; Yu-Juan Xu; Yuan-Shan Yu (Carbohydrate Polymers, 2026)

Overexpression of the tomato SlSAMS1 gene reshapes rhizosphere bacterial communities and soil metabolomes to alleviate alkali stress - Simin Li; Qinghua Shi; Na Sui; Fenghui Wu (Applied Soil Ecology, 2026)

Crop rotations modulate chemical transformation of dissolved organic matter during mineral surface-bound Fe(II) oxidation in paddy soils - Cong Wu; Fangling Li; Taoyuan Ouyang; Wei Peng; Yanqi Xiao; Fu Liu; Qihong Zhu; Na Zhang; Hao-Jie Cui; Wenjuan Liao (Applied Geochemistry, 2026)

Species Divergence in Oxytocin-Dependent Yawning on a Conserved Glutamatergic Erection Circuit - Yan-Chu-Fei Zhang; Qing-Wu Zheng; Yang Lu; Hao-Yuan Wang; Jiao Cang; Xin-Rui Wu; Lin-Yao Fan; Liang Li; Ni-Na Zhang; Xiao-Yang Zhang; Jing-Ning Zhu; Jian Jing; et al. (Neuroscience Bulletin, 2026)
Yawning coupled with penile erection is a conserved neurobehavioral syndrome mediated by the paraventricular hypothalamus (PVH). However, the distinct roles of oxytocin and its co-transmitters remain unresolved. Using chemogenetics, we showed that activation of PVH oxytocin neurons was sufficient to elicit both responses, whereas silencing these neurons abolished them. Viral tracing revealed that these neurons project collaterally to the brainstem reticular nucleus and spinal cord to spatially coordinate autonomic and somatic motor outputs. By dissecting the molecular mechanisms using CRISPR-Cas9, we found that vesicular glutamate transporter 2 (VGLUT2)-dependent glutamatergic transmission provides the primary drive for both behaviors, whereas the oxytocin peptide is selectively required for yawning but dispensable for erection. Comparative analyses across rats, hamsters, and mice demonstrated that while the glutamatergic erectile circuit was conserved, mice lacked spontaneous yawning and were resistant to apomorphine-induced yawning. These findings suggest a hierarchical co-transmission framework in which fast glutamatergic signaling provides the core drive, while oxytocin confers behavioral specificity.

Galectin-3 in systemic lupus erythematosus: a meta-analysis - Yang Wu; Li-Na Jiang; Jing-Ru Wu; Yi-Ran Lu; Ting-ting Lu; Ji-Min Zhu; Jing Li; Shanshan Xu; Bai-Kun Li; Cheng-Gui Miao; Yan-Mei Mao (Immunologic Research, 2026)

Retraction notice to “Algorithm developed for dynamic quantification of coal consumption for and emission from rural winter heating” [Sci. Total Environ. 737 (2020) 139762] - Yuzhe Zhang; Guorui Zhi; Sicong Guo; Wenjing Jin; Lei Wang; Jinhong Du; Miaomiao Cheng; Zhigang Xue; Yisheng Xu; Rong Shi; Yajing Lu; Hongyan Dang; et al. (Science of The Total Environment, 2026)

The cytokinin oxidase/dehydrogenase MdCKX4 regulates drought tolerance in Malus domestica - Tong Li; Yu-Feng Zhang; Joy Xin-Yue Zhai; Zi-Quan Feng; Shuo Ma; Xin-Yi Li; Huai-Na Gao; Long-Xin Luo; Zhi Li; Qi Zhang; Min-Min Zhou; Ya-Li Zhang; et al. (Plant Science, 2026)

Association of single and combined metal burdens with systemic immune inflammation in smelter workers: A population-based study - Di Wu; Yuankai Cheng; Shuxian Wang; Na Wang; Danhua Zhang; Zhaoyan Wang; Jianxia Cao; Yuzheng Li; Yanhong Li; Jinrui Ma; Yingzheng Zhao; Sihua Wang (Journal of Trace Elements in Medicine and Biology, 2026)

Identifying driving factors of lacustrine groundwater discharge in Lake Taihu with integrated surface-subsurface numerical modeling - Hao Zhou; Yadong Shi; Yue Zou; Ya Jiang; Na Zheng; Subin Cheng; Donghao Wu; Xin Luo; Chaomeng Dai; Juntao Zheng; Zhi Li (Journal of Hydrology, 2026)

Enhanced removal of polycyclic aromatic hydrocarbons (PAHs) by biochar-immobilized laccase: Stability, reusability, and mechanistic insights - Longmiao Yuan; Jiayan Li; Yuting Wang; Xiaofeng Ma; Na Liu; Yingqin Wu; Beihang Zhang; Qiaohui Fan (Journal of Environmental Chemical Engineering, 2026)

Selective suppression of key hazardous asphalt VOCs by MIL-101: From risk screening to mechanistic insights - Jinyi Wu; Na Li; Habib Ullah; Zakir Zaman Khan; Jianlin Feng; Yu Song; Quantao Liu; Shaopeng Wu; Jianying Yu (Journal of Cleaner Production, 2026)

Biotransformation of 2-Aminobenzothiazole by a newly isolated Rhodococcus sp. YQ-4 eliminates its toxicity to sensitive organisms - Fuyu Song; Jiaxi Liu; Qi Wu; Aiqin Diao; Yinhu Jiang; Xin Yan; Na Li; Jian He; Jiguo Qiu (International Biodeterioration & Biodegradation, 2026)

Foliar ammonium nitrogen at booting stage enhances 2-acetyl-1-pyrroline, modulates functional compounds, antioxidant activity, and head rice yield in fragrant rice - Guanhao Huang; Na Chen; Yingling Wu; Fukang Li; Xinyu Chen; Jiemei Peng; Zhilong Chen; Hua Tian; Zhaowen Mo (Food Research International, 2026)

Stem Cell and Stem Cell-Derived Extracellular Vesicles: Therapeutic Potential and Mechanistic Insights in Anti-Aging - Jinfeng Liu; Dong Li; Shuxing Wu; Na Liu (Stem Cell Reviews and Reports, 2026)

Pollutant-specific carbon footprint analysis and decarbonization potential for municipal wastewater: A case study in Xi'an, China - Zhaoqing Wang; Yiwen Ouyang; Dungang Gu; Liqing Wu; Wenqi Zhang; Guanghui Li; Jifa Liu; Zelin Wang; Na Wei; Shijie Yuan; Jiaqi Lu (Journal of Environmental Management, 2026)

Expanded coverage of N-acyl amino acids using one-pot micro synthesis-chemical derivatization-LC-MS strategy: A key to bioactive compounds analysis in fermented soybean - Jie Han; Yujie Li; Lanjia Ao; Li Zhang; Tingting Zhou; Na Li; Jian-Lin Wu (Food Chemistry, 2026)

Aggregation-disaggregation cycling: A physical strategy for low-viscosity fish protein particles - Xueer Yu; Xinyao Zhao; Bowen Zou; Aijun Jian; Jiaxin Li; Xianbing Xu; Ming Du; Chao Wu; Xiaokang Na (Food Chemistry, 2026)

Selenomethionine antagonizes sodium arsenite-induced reproductive toxicity in zebrafish - Yan Zhang; Huan Wang; Xinru Bo; Yangfan Xu; Lingtian Xie; Yunyang Li; Jingli Mu; Jialing He; Na Zheng; Baoquan Zhao; Hongxing Chen; Wu Dong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

A surface-engineered mycelial biofilm incorporating a self-cascading nanozyme for mycotoxin degradation in edible oils - Xue-ming Cao; Xue-ting Zhu; Yang-yang Geng; Ruo-mu Xia; Jin-min Zhang; Li-na Wu (Chemical Engineering Journal, 2026)

Detachable TMSD-CRISPR for programmable and highly specific discrimination of DNA/RNA mutations - Yiqi Zhang; Wang Luo; Yaoyi Zhang; Yu He; Li Zhang; You Wu; Kejia Wu; Hongyan Yu; Xiaole Han; Na Yin; Jiu Pu; Dan Bai; et al. (Chemical Engineering Journal, 2026)

Self-assembling gardenia pectin gel for cholestatic liver injury: Dual mechanisms of hepatoprotection via PPARα activation and gut microbial modulation - Lanjia Ao; Yujie Li; Lingling Zheng; Xiaolin Chen; Haoyuan Zeng; Wen Miao; Shuxian Yang; Tingting Zhou; Na Li; Jian-Lin Wu (Carbohydrate Polymers, 2026)

A Humanized Knock-in Mouse Model of the PSEN1 V97L Mutation from a Major Chinese Alzheimer’s Disease Pedigree Reveals Early Neuroinflammation - Lu Dai; Sirong Lv; Huimin Guo; Zizhao Li; Jiaying Li; Yujia Wang; Miaomiao Du; Donghui Wu; Kunhe Ma; Na Wu; Jing Zhang; Baian Chen (Neuroscience Bulletin, 2026)

Integrated NGS-MassARRAY Screening Reveals Hidden Wilson Disease Burden - Jia Tang; Hao Geng; Haihong Shi; Ting Yu; Jinping Qiao; Qingjiang Guo; Kun Wang; Jingjing Jiang; Qing Zhao; Na Nian; Yun Cheng; Shijing Wang; et al. (Phenomics, 2026)

A novel UAV-based fusion of spectral and textural features with canopy stratification for accurate estimation of vertical nitrogen distribution in cotton - Guldana Sarsen; Qiu-xiang Tang; Ya-bin Li; Long-long Bao; Yu-hang Xu; Guang-yun Sun; Jian-wen Wu; Yierxiati Abulaiti; Qing-qing Lv; Fubin Liang; Na Zhang; Ren-song Guo; et al. (Computers and Electronics in Agriculture, 2026)

Functional differentiation of DOM is coupled with nitrogen cycling in large reservoirs along an altitudinal gradient: Antagonism between condensed aromatics and carbohydrates is associated with retention and removal - Chen Li; Wei Wu; Hang Chen; Lei Ren; Sheng Xu; Zeyu Xiao; Na Zhang; Yuxuan Shi (Journal of Hydrology, 2026)

Application of rice husk biochar in foam lightweight filler: Investigating sustainable development potential of innovative subgrade materials - Erlu Wu; Pengfei Wei; Na Li; Ping Jiang; Wei Ding; Wei Wang (Journal of Environmental Chemical Engineering, 2026)

Corrigendum to “Effects of quinoa addition on physicochemical properties, microbiome profiles, and volatile organic compounds in medium-temperature Daqu” [Food Res. Int. 223 (2026) 117868] - Wei Cheng; Chao Jiang; Tianquan Pan; Qingyun Zhu; Gengdian Liu; Na Li; Zaijie Wu; Xingjiang Li (Food Research International, 2026)

Impact of freezing storage on the structure integrity of pectin in Eureka lemons - Wen-Yu Gao; Ya-Xin Li; Na Ai; Sheng-Jiao Lei; Meng-Die Wu; Jun-Qian Wu (Food Chemistry, 2026)

Time-dependent biphasic dysregulation of autophagy and innate immunity underlies polystyrene microplastics-induced hepatotoxicity in Nile tilapia - Feilong Wang; Xiaomeng Guo; Na Guo; Xiaolong Fan; Haiyan Xu; Yuanyuan Li; Tian Gao; Yixin Chen; Changle Zhao; Lina Sun; Deshou Wang; Xin Xie; et al. (Aquatic Toxicology, 2026)

Defining and valuing reservoir ecosystem services: A unified framework and large-scale assessment of 400 representative Chinese reservoirs - Haoyan Ma; Lili Xu; Baolin Li; Jiabin Wu; Na Chen (Applied Geography, 2026)

How does residential and daily green space exposure promote individual mental health in the suburbs? A study via multiple pathways - Hong Li; Jiayu Wu; Na Ta (Applied Geography, 2026)

Regulated cell death: a multidimensional regulatory network in the pathogenesis of renal fibrosis - Wen Li; Liang Zhou; Jinji Zhang; Jingying Sun; Qing Feng; Kunyi Wu; Na Zhu (Apoptosis, 2026)

Single-cell profiling and machine learning identify cuproptosis-related fibroblast subpopulations and fibrogenesis modulator AEBP1 in endometriosis - Erqing Huang; Jiang-Tian Li; Danhui Zuo; Ruijie Li; Qingyue Wu; Na Lin; Jinru Zhao; Huajing Wang; Yi Liu; Ling Zhang (Apoptosis, 2026)

DICP1-A precisely degrades STING-A but not STING-B to suppress IFN expression through the autophagic pathway in gibel carp - Yue Wu; Shun Li; Fan-Xiang Gao; Zhi Li; Rui-Hai Gan; Can Zhang; Xiao-Li Yang; Zhuo-Cong Li; Chu-Jing Zhou; Yang-Yang Wang; Na Xu; Xue-Bing Wang; et al. (Aquaculture, 2026)

The interaction between DNA methylation and single-nucleotide polymorphism in regulating the mRNA expression of CYP1A1, GSTP1 and GSTM1 in population - Aixiang Liu; Yuxin Shi; Xin Li; Miao Wu; Tingyi Zhao; Yingying Wu; Na Xia; Hongmei Zhang (Toxicology Letters, 2026)

Identification of novel genes involved in pediatric congenital heart disease using trio-based whole genome sequencing - Bo Wang; Mo Li; Wei Zhou; Huiwen Chen; Ying Xiang; Guocheng Shi; Guoling You; Luan Chen; Yesheng Zhang; Xiaoqing Zhang; Yunqian Gao; Lulu Li; et al. (Science Bulletin, 2026)

Impact of habitat biotic factors on selective food hoarding in Brandt's voles - Shan-shan Sun; Tao Liu; Hai-rui Yang; Zhi-liang Zhang; Ya-nan Li; Ming Ming; Hao-ting Zhang; Hai-wen Yan; Xin Li; Lin-lin Li; Na Zhu; Xiao-dong Wu; et al. (Journal of Arid Environments, 2026)

Mechanisms by which different structures and compositions of exogenous proteins modulate the physicochemical properties of rice starch gels and the textural characteristics of rice noodles - Chenchen Wu; Chunyan Jia; Ming Wu; Zhuohang Li; Guang Zhang; Xiaofei Liu; Na Zhang (Food Hydrocolloids, 2026)

Structural characterization and anti-inflammatory evaluation of a novel galacturonic acid-rich polysaccharide from green walnut husk (Juglans regia L.) - Na Li; Xi Feng; Yongping Xu; Shuying Li; Yeli Zhang; Likuo Fan; Xiaoying Wu; Lina Dong (Food and Bioproducts Processing, 2026)

Key enzymes in N6-methyladenosine modification regulate plant stress tolerance by modulating mRNA stability - Zishuo Han; Hongxiang Zheng; Yinping Gao; Simin Li; Zengting Chen; Fangning Zhang; Fenghui Wu; Zhiying Zhao; Lei Yan; Na Sui (Plant Cell Reports, 2026)

Crystal phase-dependent ZrO2 for fluoride adsorption in hydrochloric acid - Qian Wu; Xin Huang; Shiyu Sun; Yan Li; Fengzhen Liu; Xin Chen; Na Wang; Ting Wang; Zijian Zhou; Bin Lu; Hongxun Hao (Journal of Environmental Chemical Engineering, 2026)

Asynchronous abrupt changes of lake ecosystems in the Anthropocene - Dinggui Wu; Tian Xia; Qingfeng Zhao; Yibin Sun; Na Song; Man Li; Tianchen He (Global and Planetary Change, 2026)

Synergistic stabilization of cationic and anionic redox in lithium-rich cathodes via an O2-type surface layer - Yang Zhang; Jiyang Li; Yiqi Wang; Zhen Ge; Aigang Zhen; Na Li; Tingting Feng; Mengqiang Wu (Chemical Engineering Journal, 2026)

Enhanced metal-organic framework-driven deep learning-assisted magnetic crystal paper aptsensor for two-step sensitization and in-situ detection of pathogenic bacteria - Lulu Cao; Yuwei Ren; Shengshi Jiang; Hui Li; Maoling Hu; Xin Zhang; Xiaoyu Yu; Weichao Wu; Mengyu Li; Zhao Liang; Na Ling; Hongzhou Chen; et al. (Chemical Engineering Journal, 2026)

Global rare earth trade dependence network: evolution, mechanism and climate mitigation implications - Chunbao Ge; Jie Liu; Na Li; Nan Lu; Gang Wu (Theoretical and Applied Climatology, 2026)

Functional trait variation of Rhododendron aureum in relation to Deyeuxia angustifolia encroachment in an alpine tundra - Na Li; Zhaoyong Hu; Guangqi Zhang; Mai-He Li; Zhengfang Wu; Renkai Dong; Suke Hou; Chao Song; Haibo Du (Plant and Soil, 2026)

Mobilization and redistribution of Arsenic during intense weathering of granite, eastern Tibetan Plateau, China - Zi-Han Xia; Jun-Wen Zhang; Na Wu; Mei-Li He; Qi Liu; Zhi-Qi Zhao (Environmental Geochemistry and Health, 2026)

Pyocyanin induces rice benzoxazinoid synthesis to co-drive cadmium immobilization in rhizosphere microdomain: Microbial metabolite-mediated spatiotemporal communication mechanisms - Shengwei Yi; Zan Tian; Lanlan Wei; Feng Li; Lizhong Zhu; Fangbai Li; Songxiong Zhong; Fei Ge; Na Liu; Xionghui Ji; Jiang Tian; Yujun Wu (Soil Biology and Biochemistry, 2026)

RBOHC-derived ROS control plant nitrate starvation response via WRKYs-activated expression of high-affinity nitrate transporters - Tian Yuan; Meng-Qi Cui; Chen Xu; Jing-Ying Yan; Wo-Na Ding; Ji-Ming Xu; Yun-Rong Wu; Gui-Xin Li; Yu Liu; Dong Zhang; Chuan-Zao Mao; Moussa Benhamed; et al. (Science Bulletin, 2026)

Longitudinal profiling of toxigenic fungi and mycotoxin risks in Coix lacryma-jobi L. - Anqi Xu; Yan Xu; Yuhui Yang; Fan Sun; Hua Cai; Yin Zhu; Xiaohui Xu; Xiushi Li; Aibo Wu; Na Liu (Journal of Hazardous Materials, 2026)

Advancements in metal-organic frameworks for alkaline oxygen evolution reaction: mechanistic insights, catalyst stability and applications - Ruo-Jin Liu; Xue-Ying Yang; Zheng-Yi Wu; Na Xu; Fu-Li Wang; Ren-Qing Lv; Guanqun Han; Bin Dong; Yong-Ming Chai (Fuel, 2026)

Potent dual-function of marine peptide N6NH2 and its D-enantiomer to combat MDR A. veronii infection in tilapia (GIFT, Oreochromis niloticus) - Ting Li; Na Yang; Da Teng; Ruoyu Mao; Ya Hao; Huihui Han; Yankang Wu; Xiumin Wang; Jianhua Wang (Fish & Shellfish Immunology, 2026)

Multifunctional pomelo peel cellulose/lysine/ZIF-8 porous foam with honeycomb structure: Adsorption performance and mechanism - Haize Su; Weipeng Qiu; Tenggen Hu; Shaohua Luo; Jinling Wu; Xiaowen Zhong; Na Li; Hao Su; Zhizhou Ling; Zhenlin Xu; Hong Wang; Peng Wen (Carbohydrate Polymers, 2026)

Modulation mechanisms of seasonal PM2.5 by 2D/3D urban morphology under background meteorological conditions: Insights from a GAM-based analysis - Mengbo Wu; Na Liu; Jingyi Wei; Xinxin Xia; Tianqi Li; Junyi Li; Zhipeng Zhu (Atmospheric Pollution Research, 2026)

Comprehensive Evaluation of Maize Material Production and Nitrogen Utilization in Saline-Alkali Land Under Different Nitrogen Application Levels Based on EWM-TOPSIS-AISM Models - Weifan Liu; Hao Liu; Fenglan Ma; Menghu Wan; Tao Li; Xiaoying Ma; Yong Cui; Linfeng Huang; Jili Liu; Na Wu (Journal of Soil Science and Plant Nutrition, 2026)

Two new abietane diterpenoids from Salvia cavaleriei var. simplicifolia - Qian Wu; Jie Yang; Mi-Na Yang; Li-Jia Ye; Hong-Fen Jiang; Miao Zhang; Xin Wang; Yi-Nan Yang; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2026)

Nigrospora aurantiaca causes leaf spot disease in Bletilla striata in China - Na Wu; Zhen Su; Junyi Gao; Dengquan Liu; Maoxian Wang; Zhongshun Cai; Cheng Li (Crop Protection, 2026)

Long-term waterproof performance of EPDM sealing gaskets considering aging-induced stress relaxation - Hua-Yong Li; Huai-Na Wu; Hong Cao; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2026)

Millennial- to centennial-scale record of organic carbon accumulation and its periodic occurrence in the Yellow Sea since the last deglaciation - Yuying Zhang; Limin Hu; Yazhi Bai; Lina Jin; Hyung Jeek Kim; Na Li; Song Zhao; Jun Ye; Yonghua Wu; Xiao Wu; Xiting Liu; Xun Gong; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Antibiotic resistance genes against “last-resort” antibiotics within the One Health framework: Dissemination, mechanisms, and AI-driven opportunities - Yining Wu; Lin Zhu; Na Li; Chuze Lu; Chengdong Zhang; Meizhen Wang (Journal of Hazardous Materials, 2026)

Impacts of iron additives on enzymatic activities and nitrogen cycling during composting: Microbial and biochemical insights - Yang Wang; Hong-Yi Wu; Shuang-Yan Jia; Hao-Duo Bai; Kuok Ho Daniel Tang; Xiu-Na Ren; Zhixin Zhang; Yao Yiqing; Guo Xiaohui; Chugang Mei; Rong-Hua Li (Journal of Cleaner Production, 2026)

Study on mechanical properties of non-diagenetic hydrates-bearing sediments under in-situ static conditions - Na Wei; Jiang Wu; Haitao Li; Jun Pei; Shouwei Zhou; Jinzhou Zhao; Bjørn Kvamme; Richard Banks Coffin; Anping Feng; Jianyong Feng (Fuel, 2026)

Integrative metabolomics-assisted comprehensive components analysis of complex system (CCACS) revealed functional potential: Valorization of gourd fruit (Trichosanthes kirilowii maxim.) - Wen Miao; Na Li; Lanjia Ao; Yujie Li; Ying Liu; Yiran Zhao; Xiaolin Chen; Yuyao Wu; Jian-Lin Wu (Food Research International, 2026)

Self-driven degradation and protection against chemical warfare agent simulants via MOF-808 derived bipolar membrane interfaces - Na Gao; Xiao-Peng Li; Xinbo Wang; Li Li; Heguo Li; Fen Luo; Yue Zhao; Huan Xu; Liang Wu (Chemical Engineering Journal, 2026)

Natural variation in VrERF088 modulates drought tolerance during mungbean germination - Xi Zhang; Jinyang Liu; Shicong Li; Yun Lin; Yixiang Pu; Qiang Yan; Jingbin Chen; Ranran Wu; Na Yuan; Prakit Somta; Lixia Wang; Xin Chen; et al. (Theoretical and Applied Genetics, 2026)

Shoreline changes along the coast of mainland China over the past four decades - Hongzhen Tian; Kai Xu; Qinping Liu; Chengxiu Li; Na Wei; Zheng Wu; Zheng Zhang; Xuedan Zhang; Guoquan Li (Journal of Coastal Conservation, 2026)

Codon usage biases in the chloroplast genomes of 27 Ardisia species - Shengqun Chen; Dongbo Wu; Ai Rao; Na Hou; Yueyun Wang; Mao Li (Acta Physiologiae Plantarum, 2026)

Enhancing Blood Fingerprints with Multicolored Conjugated Polymers: A Fluorescent Strategy with Python-Based Quantitative Assessment - Zimin Zhang; Yuhao Zhang; Xuelian Jiang; Na Rao; Mingzhu Wu; Ying Li; Di Peng (Journal of Fluorescence, 2026)

Prediction on the waterproof performance of EPDM gaskets in shield tunnels considering the stress state of compression and tension - Ren Wu; Huai-Na Wu; Hua-Yong Li; Xin-Xin Yang; Dong-Lin Feng; Hong Cao; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2026)

Application of an innovative BMask R-CNN-DAT enhanced with feature extraction and boundary awareness in tunnel leakage detection - Yu Li; Huai-Na Wu; Hong-Zhan Cheng; De-Sai Guo; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2026)

Three-dimensional suspension induction of porcine EPSCs into PGCs - Liming Yuan; Xiaolong Wu; Xiaoxiao Fu; Zuo Lei; Hongzhao Shi; Wenjie Xu; Yaya Zhao; Jiannan Li; Xueting Li; Lexi Gao; Na Li; Jinlian Hua (Theriogenology, 2026)

Pinoresinol diglucoside alleviates hindlimb unloading-induced bone loss in mice - Ying-Ying Xuan; Liang Li; Yi Wu; Zhen-Long Wei; Mei Zhang; Min-Na Liu; Dong-Shuai Shen; Yu-Hai Gao; Cory J Xian; Hui-Ping Ma; Ke-Ming Chen (Life Sciences in Space Research, 2026)

Dual-functional Mn-single atom catalysts for synergistic H2O2 generation and activation: Toward efficient refractory organic wastewater treatment - Chen Yu; Dawei Liang; Chao Qu; Na Ren; Qinghao Wu; Xiaohu Li; Jingjing Yao (Journal of Hazardous Materials, 2026)

NADH-driven bioreductive degradation of azo dyes: Mechanisms of high NADH production, electron transfer, and microbial responses - Yiting Qin; Xuehui Xie; Dongyang Li; Ziyi Wu; Jiajie Liu; Wanting Li; Daijie Tang; Songwei Chen; Yiwen Zhang; Na Liu; Qingyun Zhang; Ye Chen (Journal of Hazardous Materials, 2026)

Effects of quinoa addition on physicochemical properties, microbiome profiles, and volatile organic compounds in medium-temperature Daqu - Wei Cheng; Chao Jiang; Tianquan Pan; Qingyun Zhu; Gengdian Liu; Na Li; Zaijie Wu; Xingjiang Li (Food Research International, 2026)

Nutritional regulation by vitamin A: Comprehensive impacts on growth, molting, immunity, lipid metabolism, and ovarian maturation in red swamp crayfish (Procambarus clarkii) - Jiacheng Yu; Siying Hu; Fuxian Zhang; Donglin Cui; Yihan Wu; Runyu Li; Na Li; Chengmin Zhao; Kai Luo; Weihua Gao; Shouqi Xie (Fish & Shellfish Immunology, 2026)

Surface functional groups related organic fouling on polyamide membranes: A molecular dynamics study - Na Li; Bingyan Wu; Jiulong Yin; Meng Li; Xuan Zhang (Desalination, 2026)

Development and validation of a multiplex high-risk HPV detection method using lyophilized microsphere technology and multicolor melting curve analysis - Miao Fu; Huabin Wang; Yingchao Wu; Chaoyong He; Wei Chen; Na Zhang; Xin Chen; Jinhua Wang; Xiaohuan Zhao; Meili Lin; SiSi Mao; Xi Xiang; et al. (Chemical Engineering Journal, 2026)

Hepatic cyp24a1 serves as a biomarker for diagnosing polystyrene microplastic exposure in Nile tilapia (Oreochromis niloticus) - Feilong Wang; Haiyan Xu; Xiaomeng Guo; Xiaolong Fan; Yuanyuan Li; Tiao Gao; Xin Xie; Na Guo; Fan Bai; Yixin Chen; Changle Zhao; Deshou Wang; et al. (Aquatic Toxicology, 2026)

Dynamics of bacterial community and fermentation quality of wheat straw silage treated with lactic acid bacteria and/or sucrose - E. Li; Na Na; Nier Wu; Wencan Ke; Chunsheng Bai; Yanlin Xue (Animal Feed Science and Technology, 2026)

Novel interface-enhanced bimetallic nanozyme-mediated magnetic integrated nanoplatform for integrated prevention and control of pathogenic bacteria - Xiaoyu Yu; Xin Zhang; Yuwei Ren; Rui Jiao; Hui Li; Mengyu Li; Weichao Wu; Na Ling; Danfeng Zhang; Jianghua Cheng; Yingwang Ye (Analytica Chimica Acta, 2026)

Nuclear transport factor IPO4 modifies localization by PCV2 and facilitates viral replication - Cui Lin; Chengcheng Wu; Fanfan Zhang; Na Li; Haiqin Li; Lihan Tao; Jia Tan; Yanbing Zeng; Shaopei Fang; Quanyong Zhou (Veterinary Microbiology, 2025)

Influence of multidimensional spatial factors on urban park cooling and carbon-saving effects: Insights under contrasting background meteorological conditions - Zhipeng Zhu; Mengbo Wu; Yinghong Ding; Na Liu; Jingyi Wei; Fangbing Hu; Xiong Yao; Junyi Li (Sustainable Cities and Society, 2025)

Mechanical properties of monolithic EPS-coated lightweight soil: unconfined compressive strength and small-strain dynamic characterization - Ping Jiang; Xinghan Wu; Wei Wang; Na Li; Haihua Zhan; Guoxiong Mei; Jianfeng Wang (Soil Dynamics and Earthquake Engineering, 2025)

Multiomic insights into the regulatory mechanism of anammox consortia: Interspecies cooperation, degradation and self-adaptation to plasticizer stress - Ge-Ge Wu; Jing-Ao Jin; Na-Na Han; Wen-Li Guo; Nian-Si Fan; Ren-Cun Jin (Journal of Hazardous Materials, 2025)

Dynamic changes in physicochemical properties, flavor, and microbial communities during kombucha fermentation with dominant autochthonous strains inoculation - E. Liao; Na Liu; Qian Li; Han Li; Lu Wang; Wenmin Wu (Food Research International, 2025)

Enhancement of stability and hydrogel properties of type-A gelatin-dextran mixtures via incorporation of whey protein isolate fibrils - Ling Wu; Die Dong; Zhengzong Wu; Jianpeng Li; Lu Lu; Na Wang; Yisu Yang; Meng Zhao; Bo Cui (Food Research International, 2025)

Unveiling the binding landscape of cinnamaldehyde with digestive proteases:An exploration of specific interactions and conformational dynamics - Yi He; Po Chen; Lijuan Chen; Wei Wang; Jingtao Pang; Yilin Li; Na Gan; Di Wu (Food Chemistry, 2025)

Influence of solid-state fermentation with lactic acid bacteria on the structure, physicochemical and adsorption properties of dietary fiber in rice bran - Dan Wang; Xiao-Tong Zhai; Na-Na Wu; Jun Li; Ming Zhao; Na Zhang; Bin Tan (Food Bioscience, 2025)

A pH-responsive prodrug biomimetic nanoplatform based on cis-aconitic anhydride-modified methotrexate for targeting therapy of oral squamous cell carcinoma - Lin Yang; Yongxiang Zeng; Na Wu; Wei Wu; Liang Chen; Li Zhu (Chemical Engineering Journal, 2025)

In situ fabrication of bacterial cellulose-based CB@Poly(ionic liquid) membranes via surfactant-free ionic liquid microemulsion: Enhanced conductivity and mechanical flexibility - Na Gao; Caiyang Zhang; Minxin Song; Jiaxing Fan; Jinyue Li; Shunjie Li; Nan Lou; Guangshun Wu; Yuyang Liu; Jian Xue; Aili Wang (Carbohydrate Polymers, 2025)

Elucidation of the biodegradation pathways of polyurethane and polyethylene terephthalate by a Fusarium strain enriched from soil-plant systems - Eyalira Jacob Okal; Yanfei Wu; Shahid Iqbal; Zhaorui Liu; Yuwei Hu; Na Hu; Tingfang Zhong; Jingxian Li; Dongmei Yu; Bishal Gurung; Dong Liu; Peter Mortimer; et al. (Bioresource Technology, 2025)

The Effect of Co-Substrates is Greater than that of Dye Structures on Decolorization and Degradation of Dyes: Comparative Study Confirmed - Xuehui Xie; Ziyi Wu; Jiao Fan; Jiajie Liu; Wanting Li; Yiwen Zhang; Songwei Chen; Na Liu; Qingyun Zhang (Water, Air, & Soil Pollution, 2025)

SOX11-mediated CBLN2 Upregulation Contributes to Neuropathic Pain through NF-κB-Driven Neuroinflammation in Dorsal Root Ganglia of Mice - Ling-Jie Ma; Tian Wang; Ting Xie; Lin-Peng Zhu; Zuo-Hao Yao; Meng-Na Li; Bao-Tong Yuan; Xiao-Bo Wu; Yong-Jing Gao; Yi-Bin Qin (Neuroscience Bulletin, 2025)
Neuropathic pain, a debilitating condition caused by dysfunction of the somatosensory nervous system, remains difficult to treat due to limited understanding of its molecular mechanisms. Bioinformatics analysis identified cerebellin 2 (CBLN2) as highly enriched in human and murine proprioceptive and nociceptive neurons. We found that CBLN2 expression is persistently upregulated in dorsal root ganglia (DRG) following spinal nerve ligation (SNL) in mice. In addition, transcription factor SOX11 binds to 12 cis -regulatory elements within the Cbln2 promoter to enhance its transcription. SNL also induced SOX11 upregulation, with SOX11 and CBLN2 co-localized in nociceptive neurons. The siRNA-mediated knockdown of Sox11 or Cbln2 attenuated SNL-induced mechanical allodynia and thermal hyperalgesia. High-throughput sequencing of DRG following intrathecal injection of CBLN2 revealed widespread gene expression changes, including upregulation of numerous NF-κB downstream targets. Consistently, CBLN2 activated NF-κB signaling, and inhibition with pyrrolidine dithiocarbamate reduced CBLN2-induced pain hypersensitivity, proinflammatory cytokines and chemokines production, and neuronal hyperexcitability. Together, these findings identified the SOX11/CBLN2/NF-κB axis as a critical mediator of neuropathic pain and a promising target for therapeutic intervention.

Novel insights into the effect of sTIM-3 on NLRP3 inflammasome via interacting with ASC - Xiaodi Zhang; Na Han; Ziqing Xu; Zheng Tong; Xiaolei Ren; Yang Sun; Chunyang Li; Xuetian Yue; Zhuanchang Wu; Xiaohong Liang; Chunhong Ma; Pin Wang; et al. (Inflammation Research, 2025)

The nonstructural protein 13 of porcine deltacoronavirus exhibits an ATP- independent and nondirectional annealing activity that is inhibited by Mg2+ - Lihan Tao; Chengcheng Wu; Cui Lin; Na Li; Shaopei Fang; Jianzhen Huang (Veterinary Microbiology, 2025)

Effect of ammonium chloride on the salt-induced cohesive behavior of egg yolk liquid and its plasma with granules - Yufei Ye; Hang Li; Na Wu; Shuping Chen; Lilan Xu; Yan Zhao; Yonggang Tu (Food Chemistry, 2025)

The embeddedness of bioactive molecules: structural characterization and functional analysis of almond protein-phloretin-L arabinose ternary complexes - Yongsong Zhang; Qian Zhou; Zun Li; Bin Wu; Chao Li; Na Xia (Food Chemistry, 2025)

Network engineering of elongated bent titanate nanotubes / cross-linked network poly(vinyl alcohol) composite membranes for pervaporation desalination - Yuping Wu; Min Li; Chen Yang; Qianting Wang; Zongli Xie; Na Li (Desalination, 2025)

Bi-directional pH-responsive cellulose nanocrystals-based pesticide microcapsules for sustainable agriculture - Jia-wei Ding; Li-na Guo; Shu-heng Li; Qin Gao; Wang Wu; De-qiang Li; Jun Li (Carbohydrate Polymers, 2025)

Effects of oat flour on rice flour and fermented rice cake: Processing properties, quality attributes, and starch digestive characteristics - Ruoyuan Xu; Zhen Dai; Xuan Wang; Jiayi Li; Yamei Jin; Na Yang; Dan Xu; Xueming Xu; Fengfeng Wu (Carbohydrate Polymers, 2025)

High-valued hexoses bioproduction from natural sugar resources: Status, trends, challenges and perspectives - Mengwei Lu; Na Li; Deming Rao; Jing Wu; Wei Xia (Bioresource Technology, 2025)

Wuhapuella caenivorax gen. nov., sp. nov., a Novel Member of the Family Weeksellaceae, a Flocculent Bacteria Isolated from an Urban Sewage Treatment Plant - Yangyang Sun; Qianzhi Wang; Shunda Qiu; Changcui Chen; Siqi Wu; Na Gao; Han Chen; Jun Yu; Chunlei Yang; Hao Li; Shijie Bai; Dongru Qiu; et al. (Current Microbiology, 2025)

Preparation and Optimization of Pramipexole Hydrochloride Solid Dispersions to Improve Drug Release and Bioavailability - Yuanyuan Ding; Zhenkun Su; Guodong Liang; Na Sai; Xin Wu; Jianping Chen; Yuheng Ma; Ruijuan Li (AAPS PharmSciTech, 2025)

The role of TRPV4 in ferroptosis in MPP+/MPTP-induced Parkinson’s disease models - Qingjie Ma; Jilin Wu; Huixian Li; Renwan Yin; Wenjing Yang; Jia Luo; Yuncheng Bai; Na Liu (Tissue and Cell, 2025)

Facile design and construction for novel sequestrators via co–functionalization of Ti3AlC2 and biochar with nano-sized FeS in efficient selenite sequestration - Wei Wang; Hongxiang Wu; Xukun Ma; Mengqi Xu; Na Li; Jiajia Fu; Hongliang Dong (Journal of Environmental Chemical Engineering, 2025)

Erratum to ‘mechanisms of exopolysaccharide synthesis by Streptococcus thermophilus IMAU20246 determined by the carbon source’[Food Chemistry 481 (2025) 144069] - Qingting Peng; Haimin Hu; Annaer Dai; Na Wu; Hong Li; Tong Dan (Food Chemistry, 2025)

A multifunctional wearable patch based on hydrogel for strain sensing and epidermal sweat-analyzing - Shihao Wu; Jingwei Lu; Hongxiao Gao; Yuemeng Yang; Na He; Gan Miao; Li-Ping Xu (Chemical Engineering Journal, 2025)

Highly efficient conversion of androstenedione into dehydroepiandrosterone through the construction of molecular machines - Minjie Li; Xiaojun Wang; Yue Fan; Xuemei Li; Yunfeng Cui; Liangyan Zhu; Xiangtao Liu; Xi Chen; Na Liu; Yanbing Shen; Jinhui Feng; Jinku Bao; et al. (Systems Microbiology and Biomanufacturing, 2025)

Dynamic WNT signaling controls differentiation of hematopoietic progenitor cells from human pluripotent stem cells - Mo Li; Keiichiro Suzuki; Mengge Wang; Christopher Benner; Manching Ku; Li Ma; Ladan Kobari; Na Young Kim; Nuria Montserrat; Chan-Jung Chang; Guanghui Liu; Jing Qu; et al. (Science China Life Sciences, 2025)

Spatiotemporal patterns of fecal cortisol metabolites in critically endangered wild Alpine musk deer in eastern edge regions of Tibetan Plateau: influencing factors and conservation implications - Jiayi Wu; Xiaoping Lu; Shuo Geng; Liquan Shen; Gong Wang; Rui Liu; Jun Qi; Chunting Feng; Junyi Yang; Zhengxu An; Rongxin Li; Na Qiao; et al. (Biologia, 2025)

UAV-based fine-scale daily relationship characterization between 3D urban surface thermal dynamics and landscape patterns - Rongyuan Dai; Fengxiang Guo; Han Zhao; Linshan Zhong; Chunyu Zhu; Na Ta; Hongqing Li; Qiong Wu (Sustainable Cities and Society, 2025)

TYROBP modulates NFκB phosphorylation and SQSTM1 expression in macrophages during Brucella Abortus LPS infection - Wenping Wu; Wenbo Chen; Shicheng Wan; Xuan Luo; Donghui Yang; Congliang Wang; Haijing Zhu; Haisheng Yu; Na Li; Jinlian Hua (Research in Veterinary Science, 2025)

Bioelectrochemistry increases the risk of resistance genes proliferation and transfer with sulfamethoxazole pressure decreasing in constructed wetlands: An overlooked double-edged effect - Xin Shan; Hutao Wang; Maozhen Han; Na Zhang; Fengling Zhang; Shaoyong Lu; Bin Zhao; Xiaohui Liu; Fengmin Li; Fengchang Wu (Journal of Hazardous Materials, 2025)

Sodium dehydroacetate induces porcine oocyte toxicity by inhibiting TCA cycle activity and mitochondrial function, with nicotinamide mononucleotide as a potential protective agent - Na Li; Yu Li; Guangjun Huang; Hongyu Sun; Jiaqi Wu; Qian Gao; Zhaokang Cui; Yilong Miao (Food and Chemical Toxicology, 2025)

Mitochondrial energy reprogramming via dECM/GP@EVs@Gpnmb to prevent post-myocardial infarction heart failure - Na Li; Ying Wang; Ling Yuan; Shuang Peng; Zhansheng Hu; Baoquan Wang; Dan Zhang; Longxiang Su; Huiping Wu (Chemical Engineering Journal, 2025)

A Co(III)-dipyrazolate framework for atmospheric CO2 photoreduction - Yingjie Wang; Xiang-Jing Kong; Guang-Rui Si; Tao He; Da-Yu Chen; Jian-Yu Zhang; Na Xing; A-Wu Zhou; Jian-Rong Li (Chemical Engineering Journal, 2025)

The Role of HbA1c in Parkinson's Disease: An Integrative Analysis by Single-Cell, Bulk Transcriptome and Mendelian Randomization - Huihe Zhang; Wei Li; Juwei Wang; Zhimin Wu; Na Zhao; Yue Jiang (Molecular Neurobiology, 2025)

Simultaneous determination of 16 herbicides in Procambarus clarkii - Na Li; Aiying Wang; Aijing Chen; Mengmeng Wu; Hongcai Liu; Yanyan Yang; Chao Wang; Dong Sun (Food Chemistry, 2025)

Polystyrene bead ingestion promotes atherosclerosis plaque progression via BMP signaling in mice - Na Yang; Bo Wu; Xiaoxue He; Junhu Ma; Longhao Dai; RuiTing Ma; Tingting Yang; Xiaoxi Ning; Xiaoyan Li; Shaobin Jia (Food and Chemical Toxicology, 2025)

Recycling traditional Chinese medicine residues: a review - Xiaowei Wu; Dai Dai; Na Li; Haixin Zheng; Cuixia Wang; Weixiong Lin; Liaoyuan Liu; Zheng Zhang; Jörg Rinklebe; Carol Sze Ki Lin; Wen Rui; Chong Li (Environmental Chemistry Letters, 2025)
Traditional Chinese medicine has a rich history in the diagnosis and treatment of diseases, yet the disposal of medicine residues by incineration and landfilling is challenging. Here we review methods to recycle Chinese medicine residues with focus on challenges, recycling solutions, and case studies. Cases studies include extraction of bioactive compounds, use as feed additives, and biochar-based materials. We observed that residues from single-compound medicines are easier to extract and recycle into animal feed additives or adsorbents. Technical and economic analysis show that the valorisation of single-compound medicine residues is profitable. For instance, the re-extraction cost of flavonoids is 25.8–36.6% lower than the market price, and the cost as feed additives represents 14.7% of the market prices.

Cytokine profiling in COVID-19 patients by using ion mobility-mass spectrometry-based parallel reaction monitoring - Ling Yan; Chenrui Yuan; Runhou Zhou; Li Zhong; Kelvin Kai-Wang To; Na Liu; Xin Diao; Guangshan Xie; Hongzhi Zhao; Haijiang Wu; Lin Zhu; Zhiwei Chen; et al. (Analytica Chimica Acta, 2025)

Mass and heat balance of sea ice during the thaw-freezing transition in the Pacific sector of Arctic Ocean derived from the buoy measurements in 2018 - Mengqi Wu; Ruibo Lei; Bin Cheng; Long Lin; Na Li; Xiaomin Chang (Acta Oceanologica Sinica, 2025)

The driving factors and changing trends of CO2 emissions in the building sector on the Qinghai-Tibet plateau: A case study of Qinghai Province - Mengdi Wei; Zhiqi Gong; Na Li; Chengkui Liu; Jianming La; Kunlun Wu (Environment, Development and Sustainability, 2025)

Intergenerational inequity from hydrological drought in a warming world - Rutong Liu; Kebing Chen; Jiabo Yin; Biqiong Wu; Yan Zhao; Zhiming Liang; Na Li; Fengxian Gao; Jing Tian; Yujie Zeng; Jiali Guo (Journal of Environmental Management, 2025)

Mechanisms of exopolysaccharide synthesis by Streptococcus thermophilus IMAU20246 determined by the carbon source - Qingting Peng; Haimin Hu; Annaer Dai; Na Wu; Hong Li; Tong Dan (Food Chemistry, 2025)

Investigating the differences in β-Cyclodextrin derivatives / Hyperoside inclusion complexes: Dissolution properties, thermal stability, and antioxidant activity - Peiran Liu; Na Gan; Qinhong Li; Zhen Zeng; Jie Zhong; Xinhui Wang; Yanxia Sun; Di Wu (Food Chemistry, 2025)

Unveiling fungal degradation pathways for polyurethane and polyethylene through enrichment cultures and metabolic analysis - Eyalira Jacob Okal; Jie Zhou; Yanfei Wu; Tingfang Zhong; Yue Tang; Zhengyu Sun; Ruifang Xu; Yuwei Hu; Na Hu; Jingxian Li; Samantha C. Karunarathna; Peter E. Mortimer; et al. (International Biodeterioration & Biodegradation, 2025)

Effects of alkali and alkaline earth metals in biomass on co-pyrolysis characteristics and product distribution of coal and biomass - Na Liu; He Huang; Jun Feng; Rui Li; Xueli Huang; Yulong Wu (Fuel, 2025)

Characterization and gelling properties of pectin extracted from Gardenia fruit - Xuan Wang; Tian Tian; Na Li; Lingling Zheng; Yuyao Wu; Wei Bian; Jian-Lin Wu; Tingting Zhou (Food Hydrocolloids, 2025)

Structure identification and biological activity of a novel sulfated glycosaminoglycan-like polysaccharide from Sepia recurvirostra ink - Nanqi Cheng; Na Gao; Pin Wang; Yujun Ma; Pengfei Li; Xiaolu Wu; Jiaying Sun; Yulan Dai; Jinhua Zhao (Carbohydrate Polymers, 2025)

Antimicrobial Peptides: Classification, Mechanism, and Application in Plant Disease Resistance - Yuan-Zhen Wu; Jin Wang; Ying-Hui Hu; Qi-Shuo Sun; Rui Geng; Li-Na Ding (Probiotics and Antimicrobial Proteins, 2025)

Graph Neural Networks and Multimodal DTI Features for Schizophrenia Classification: Insights from Brain Network Analysis and Gene Expression - Jingjing Gao; Heping Tang; Zhengning Wang; Yanling Li; Na Luo; Ming Song; Sangma Xie; Weiyang Shi; Hao Yan; Lin Lu; Jun Yan; Peng Li; et al. (Neuroscience Bulletin, 2025)

A nine-year study: continuous application of biochar achieves efficient potassium supply by modifying soil clay mineral composition and its potassium adsorption sites - Hangming Guo; Zhengchao Wu; Jiaxin Li; Zonglin Lu; Shuxiao Luan; Shixin Hu; Xingyu Liu; Na Li; Xiaori Han (Journal of Soils and Sediments, 2025)

Cloning and Expression of the Isoprocarb Hydrolase Gene cehA from the Newly Isolated Isoprocarb-Degrading Strain Sphingobium sp. R-7 - Jing Wu; Ao Gao; Bohan wang; Yingxin Yang; Na Li; Hao Zhang (Current Microbiology, 2025)

Development of a highly efficient seeding breeding system of Notopterygium incisum - Si Cheng Yao; Qiao Jia Peng; Na Su; Yuan Yuan Jiang; Jin Qiu Liao; Long Wang; Xue Xue Deng; Rui Wu Yang; Xiang Yun Chen; Li Zhang (Plant Biotechnology Reports, 2025)

Self-assembled TMB-CuO2 nanosheets for dual-mode colorimetric and NIR-II photothermal detection of uranyl ion - Yingying Wu; Xiaofeng Tan; Hongyu Gong; Minghui Wang; Gui-long Wu; Na Li; Fen Liu; Hong Xia; Li Tang; Qinglai Yang (Analytica Chimica Acta, 2025)

Hydrogen peroxide regulated split-type electrochemiluminescence sensing platform for non-invasive detection of gastric cancer-associated D-amino acids - Juan Li; Ming-Chun Lai; Ya-Meng Zhong; Ya-Ling Chen; Na Wu; Wei Chen; Hua-Ping Peng (Analytica Chimica Acta, 2025)

Adsorbent application and nitrogen deep placement reduced ammonia emissions in wheat fields - Yang Yang; Weizheng Shu; Ye Yang; Xiaoyu Ni; Yuejin Wu; Wenge Wu; Na Li (Soil and Tillage Research, 2025)

Effects of freezing pretreatment on water migration and retrogradation properties of brown rice cake prepared from thermal stabilized rice bran - Jia Li; Chun Liu; Na-Na Wu; Bin Tan (Journal of Cereal Science, 2025)

Oxidative Stress-mediated Loss of Hippocampal Parvalbumin Interneurons Contributes to Memory Precision Decline After Acute Sleep Deprivation - Yu-zhu Gao; Kai Liu; Xin-miao Wu; Cui-na Shi; Qiu-li He; Hai-peng Wu; Jian-jun Yang; Hao Yao; Mu-huo Ji (Molecular Neurobiology, 2025)

Harnessing corn straw biochar: A breakthrough in eco-friendly Cu(II) wastewater treatment - Na Li; Fuchen Zhu; Zhaowei Wang; Jinghui Wu; Yidi Gao; Keqing Li; Chunliang Zhao; Xianze Wang (Waste Management, 2025)

Brain-targeted delivery of Acetyl-11-Keto-β-Boswellic acid with enhanced anti-inflammatory efficacy via blood-brain barrier peptide shuttle PepH3 - Na Cui; Tingting Fan; Liang Li; Wei Liu; Mingjie Li; Mukun Huang; Qianwen Wu; Jingwen Wang; Wenbin Zhang; Shengzheng Wang; Yi Ding (Chemical Engineering Journal, 2025)

An extensin-like gene OsPEX1 plays key roles in temperature stress response in rice - Jieni Li; Ao Li; Yue Wang; Zhi-Hao Wu; Xiaohong Li; Jie Meng; Chen Liang; Yuxin Song; Na Liu; Wanzhen Gao; Haifeng Peng; Yingxue Yang; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Frost-heaving may triggered the catastrophic landslide in Zhenxiong on January 22, 2024 - Mingyang Wu; Anhui Li; Zhi Li; Ningsheng Chen; Shufeng Tian; Runing Hou; Jules Maurice Habumugisha; Na Huang (Landslides, 2025)

Pathogenic characterization and drug resistance of neonatal sepsis in China: a systematic review and meta-analysis - Ruixue Wu; Xiaoyu Cui; Rui Pan; Na Li; Ying Zhang; Jianbo Shu; Yang Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Immunofluorescent analysis of exosomes using a microchip filled with transparent antibody-conjugated beads for breast cancer liquid biopsy - Na Li; Cheng Cheng; Di Wu; Zixuan Song; Bei Wang; Guiying Li; Fang Yang (Analytica Chimica Acta, 2025)

Waterproofing enhancement mechanism of the double sealing gaskets: Experimental test and theoretical analysis - Hua-Yong Li; Huai-Na Wu; Dong-Lin Feng; Lei Liu; Qing-long Cui; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2025)

Nitrification inhibitor induced microbial NH4+-N immobilization improves maize nitrogen use efficiency in strong ammonia oxidation soil - Si-Yi Liu; Di Wu; Xiao-Tang Ju; Ju-Pei Shen; Yi Cheng; Na Deng; Xiao-Tong Song; Hong-Jie Di; Pei-Pei Li; Li-li Han; An-Hui Ge; Chuan-Fa Wu; et al. (Soil Biology and Biochemistry, 2025)

A PRA-Rab trafficking machinery modulates NLR immune receptor plasma membrane microdomain anchoring and blast resistance in rice - Di Liang; Dongyong Yang; Tai Li; Zhe Zhu; Bingxiao Yan; Yang He; Xiaoyuan Li; Keran Zhai; Jiyun Liu; Yoji Kawano; Yiwen Deng; Xu Na Wu; et al. (Science Bulletin, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

Genome-wide identification and analysis of autophagy-related (ATG) genes in Lycium ruthenicum Murray reveals their crucial roles in salt stress tolerance - Yi Shi; Yan Wu; Mengling Li; Na Luo; Faqiang Li; Shaohua Zeng; Ying Wang; Chao Yang (Plant Science, 2025)

The effect of chloride ion on the reinforcement of zero-valent copper activated peroxysulphate - Peng Xu; Na Li; Pengfei Zhu; Ruoxi Wu (Journal of Water Process Engineering, 2025)

Synergistic effects of salinity and biochar on enhancing ethanol-fed anaerobic digestion under elevated organic loading - Tongyu Wu; Ziling Wang; Na Yang; Yuheng Huang; Yizhen Zhang; Yang Li (Journal of Water Process Engineering, 2025)

A framework for the construction of effective landscape ecological network with integrating hydrological connectivity: A case study in Dongjiang River Basin, China - Xin Jiang; Zhi-Yun Jiang; Zhen-Ya Li; Jie Su; Li-Na Tang; Meng-Di Wu; Yi-Jia Wang (Journal of Environmental Management, 2025)

Corrigendum to “A comparative investigation on the extraction-function relationship of polysaccharides derived from Moringa oleifera seeds in terms of antioxidant capacity” [Food Chem. 465 (2025) 142137] - Hongru Yang; Chongbin Lei; Dongyao Li; Na Zhang; Yumiao Lang; Liping Wu; Miaoshu Wang; Hongtao Tian; Chen Li (Food Chemistry, 2025)

Effect of microwave plasma processing on the structure, physicochemical properties and functional properties of rice bran protein - Chang Liu; Ning Wang; Lin Li; Dandan Wu; Liqi Wang; Na Zhang; Dianyu Yu (Food Hydrocolloids, 2025)

In vitro antioxidant activity of the polysaccharide from Auricularia auricula and its structural characterisation - Min Lei; Mengqing Wang; Wentao Ma; Na Li; Jiwen Huang; Xinjian Jiang; Wenhui Wu; Chaoyan Zhang (Natural Product Research, 2025)

KCNJ15 inhibits chemical-induced lung carcinogenesis and progression through GNB1 mediated Hippo pathway - Hong-qiang Chen; Na Wang; Yong Zeng; Yu Shi; Zhe Zhang; Jiang-ying Li; Ya-wen Li; Shuang-wu Deng; Zi-yuan Zhou; Wen-bin Liu (Toxicology, 2025)

Association between maternal serum zinc and birth weight is modified by neonatal SOD2 polymorphism and promoter methylation - Yuting Zeng; Yalong Wang; Yanan He; Qinyang Li; Ruiqin Chen; Cuiping Wu; Na Li; Xinya Cheng; Yuhui Du; Fangfang Yu; Yue Ba; Guoyu Zhou (Journal of Trace Elements in Medicine and Biology, 2025)

An unexpected accelerated-fabrication of high-flux CHA-type zeolite membranes enabled by creating silanol nests in their seeds - Ni Liu; Huizhi Zhang; Yonghui Ma; Yuhan Li; Tian Gui; Meihua Zhu; Xiaowei Wu; Na Hu; Xiangshu Chen (Journal of Environmental Chemical Engineering, 2025)

Remediation of various phenanthrene-contaminated soils using persulfate-Pseudomonas aeruginosa GZ7: Soil properties, radical formation, and microbial community - Na Liu; Xiangyuan Zhou; Lin Wu; Tao Jin; Kang Li; Liping Wang (Journal of Environmental Chemical Engineering, 2025)

A comparative investigation on the extraction-function relationship of polysaccharides derived from moringa oleifera seeds in terms of antioxidant capacity - Hongru Yang; Chongbin Lei; Dongyao Li; Na Zhang; Yumiao Lang; Liping Wu; Miaoshu Wang; Hongtao Tian; Chen Li (Food Chemistry, 2025)

Characterization of the effects of bridging linker on the β-Lactoglobulin binding mechanism on the nanoscale metal-organic frameworks - Na Gan; Yali Song; Yilin Li; Peiran Liu; Si Chen; Yi He; Tingting Zeng; Wei Wang; Di Wu (Food Chemistry, 2025)

Antifungal activities of Pediococcus pentosaceus LWQ1 and Lactiplantibacillus plantarum LWQ17 isolated from sourdough and their efficacies on preventing spoilage of Chinese steamed bread - Xueying Wu; Yongxin Liu; Zhengli Guo; Na Ji; Qingjie Sun; Tongjie Liu; Yang Li (Food Control, 2025)

Mass production of graphene using high-power rapid joule heating method - Dan-Na Wu; Jian Sheng; Hai-Gang Lu; Si-Dian Li; Yan Li (Chemical Engineering Journal, 2025)

N-doped biochar supported Ni-Co alloy catalyst for efficient hydrocracking of enzymatic hydrolysis lignin to monophenols in water - Zifan Wu; Yacong Deng; Fengyu Tian; Yidi Wang; Na Fan; Guangzheng Sun; Yichuan Li; Yuan Pan; Bin Liu; Bin Dong; Han Hu; Yongming Chai (Chemical Engineering Journal, 2025)

Effective enhancement of ramie anaerobic continuous flow degumming by chitosan and its microbiological mechanism - Xuehui Xie; Yiting Qin; Haonan Mo; Zhuoyu Zhao; Yuling Li; Yanxue Ma; Yao Sun; Dongyang Li; Ziyi Wu; Na Liu; Qingyun Zhang; Xiaoguang Chen (Bioresource Technology, 2025)

Ferroptosis-Related Gene Signatures in Epilepsy: Diagnostic and Immune Insights - Xueying Li; Lei Wu; Linlin Sun; Han Liu; Xuezhu Qiao; Na Mi; Shi Yan; Xinyu Zhang; Kun Wang; Pusheng Quan; Fan Yang; Lifen Yao (Molecular Neurobiology, 2025)

Composition-dependent MRM transitions and structure-indicative elution segments (CMTSES)-based LC-MS strategy for disaccharide profiling and isomer differentiation - Wen Miao; Na Li; Jia-Qian Chen; Jian-Lin Wu (Analytica Chimica Acta, 2025)

Experimental and numerical study on the waterproof performances of the sealing gaskets under coupled compression-shear stress - Huai-Na Wu; Hua-Yong Li; Lei Liu; Xin-Xin Yang; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2025)

Benzofurans and dibenzofurans from galls on twigs of the endangered Chinese endemic tree Parrotia subaequalis and their inhibitory properties against Staphylococcus aureus and ATP-citrate lyase - Peng-Jun Zhou; Xi-Ying Wu; Ze-Yu Zhao; Yi Zang; Zhong-Shuai Sun; Yue-Ling Li; Na Li; Juan Xiong; Yeun-Mun Choo; Ze-Xin Jin; Jia Li; Jin-Feng Hu (Phytochemistry, 2025)

Transparent exopolymer particles (TEP) research: From the ocean to water treatment - Ming Li; Xiang Jia; Wei Fan; Na Li; Honghai Xue; Lei Wu; Chen Lyu; Mengnan Shen (Journal of Environmental Management, 2025)

Windfarm construction alters soil multinutrient cycling by destabilizing microfauna community in a mountain ecosystem - Debao Li; Changwei Ma; Chunyu Yue; Na Lin; Yingmo Zhu; Jianping Wu (Journal of Environmental Management, 2025)

Interaction of brown rice phenolics with starch digestive enzymes and starch-iodine complex: Their effects on rice starch digestion - Fei-Fei Wu; Huan-Huan Li; Xiao-Tong Zhai; Cong-Cong Qiao; Na-Na Wu; Bin Tan (Journal of Cereal Science, 2025)

Microbiome changes and characteristics under nutrient injection for enhanced oil production at Daqing oilfield - Zi-Yue Fu; Wen-Tao Chen; Gui-Na Qi; Zhao-wei Hou; Yi-Fan Liu; Li-Bin Shou; Lei Zhou; Shi-Zhong Yang; Xiao-Lin Wu; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2025)

Screening and characterization of an antifreeze peptide from sea cucumber intestinal protein hydrolysates - Zhe Xu; ShengAo Cao; Na Cui; Rui Zhang; Zijin Qin; Hanxiong Liu; Jianping Wu; Ming Du; Zhijian Tan; Tingting Li (Food Chemistry, 2025)

Preparation and characterization of microcrystalline cellulose/corn starch-based active packaging enhanced by resveratrol/β-cyclodextrin complex - Na Yang; Haojie Sha; Wenlu Bi; Sheng Li; Shusong Wu; Dingding Su (Food Packaging and Shelf Life, 2025)

Amino oxidized sodium alginate-based humidity-resistant triboelectric nanogenerator for human motion and respiration monitoring - Xixi Wang; Na Li; Ailing Yang; Nianfeng Zhang; Wu Qiu; Dapeng Yang (Chemical Engineering Journal, 2025)

Comparative investigations on the metabolomic responses to cadmium in clams Ruditapes philippinarum from the Bohai Sea and South China Sea - Zhen Lu; Na Gao; Junfei Zhan; Shuang Wang; Chenglong Ji; Li Zhang; Huifeng Wu (Marine Pollution Bulletin, 2024)

An optimised molecular-based method for ecological study of tardigrades in soils - Zi-Yang He; Hang-Wei Hu; Keren Wu; Li Bi; Shuo Na; Anthony Weatherley; Michael Nash; Ji-Zheng He (Soil Biology and Biochemistry, 2024)

The substantial generation of photochemically produced reactive intermediates (PPRIs) in algae-type zones from one large shallow lake promoted the removal of organic pollutants - Wenkang Li; Weidong Jin; Dinggui Wu; Chunliu Wang; Huacheng Xu; Na Song (Science of The Total Environment, 2024)

Catalytic degradation of tetracycline by nano-sized Cu3V2O8 ∙H2O activated periodate: Performance and mechanism - Peng Xu; Jiafan Yao; Na Li; Jiaqi Feng; Ruoxi Wu; Baolin Hou (Journal of Water Process Engineering, 2024)

Data-driven soft sensor for monitoring effluent fecal coliform concentration in rural domestic sewage treatment - Jiaqian Yang; Guohua Li; Na Zhong; Xingren Wei; Lu Chen; Baicai Wu; Hongmei Xu; Jiangbo Zhong; Jun Li (Journal of Water Process Engineering, 2024)

Study on the strength characteristics and microscopic mechanism of sewage sludge ash modified lime soil - Wei Wang; Pengfei Wei; Na Li; Erlu Wu; Ping Jiang; Junjie Wang (Journal of Environmental Chemical Engineering, 2024)

Durable underwater superoleophobic hydrogels for oil- and Cu(II)-containing water purification - Chang-Lian Xu; Na Ji; Xingyue Wu; Xiaoxun Xu; Guiyin Wang; Zhanbiao Yang; Zhang Cheng; Shirong Zhang; Ting Li; Pietro Paolo de Oliveira e Silva; Guochun Lv; Junzhuo Cai; et al. (Journal of Environmental Chemical Engineering, 2024)

Acesulfame potassium induces hepatic inflammation and fatty acids accumulation via disturbance of carnitine metabolism and gut microbiota - Na Shou; Christopher Rensing; Qiwen Lin; Wenqian Xu; Keyi Fu; Xuefeng Yuan; Dandan Wu; Fan Wang; Yanzhong Li; Zunji Shi (Food Bioscience, 2024)

An eco-friendly, high-yield and scalable method for processing concentrated natural rubber latex with superabsorbent polymer beads - Shenbo Huang; Zirong Luo; Jizhen Zhang; Na Kong; Jihua Li; Pengfei Zhao; Jiayu Wu; Shaozao Tan; Jinlong Tao (Chemical Engineering Journal, 2024)

Design and application of a liquid metal ball-supported layered double hydroxide core–shell structure as highly efficient catalysts for the oxygen evolution reaction in rechargeable zinc-air batteries - Liqing Qiao; Wenwei Liu; Na Du; Ying Wang; Yankun Li; Haofeng wu; Zhonghua Bao (Chemical Engineering Journal, 2024)

The role of TRPV4 in programmed cell deaths - Qingjie Ma; Jilin Wu; Huixian Li; Xiaoshu Ma; Renwan Yin; Liping Bai; Heng Tang; Na Liu (Molecular Biology Reports, 2024)

Numerical Simulation of the Horizontal Water-Entry Process of High-Speed Vehicles - Jin-Long Ju; Na-Na Yang; Yi-Fei Zhang; Lei Yu; Zhe Zhang; Liang-Chao Li; Guo-Lu Ma; Wen-Hua Wu (Journal of Marine Science and Engineering, 2024)
Based on the RNG k-ε turbulence model and VOF multiphase flow model, a numerical model of horizontal water-entry of the vehicle was established, and the numerical method was verified by experimental results. The cavitation characteristics, fluid resistance, and motion of the vehicle under different conditions were studied during the vehicle’s water-entry process. The results show that the cavitation process can be divided into the cavity development stage, saturation stage, and collapse stage. With the increase in initial velocity and mass of the vehicle, more water vapor will be generated during the water-entry process. The initial velocity of the vehicle had a limited effect on the resistance coefficient. The resistance coefficient in the stable stage remained almost unchanged for vehicles with different masses. Nevertheless, the time interval of the stable stage was shortened, and the resistance coefficient was greater in the gradually increasing stage for the vehicle with a smaller mass. For vehicles with higher initial velocity or smaller mass, the instantaneous velocity decreased faster after it entered the water. The vehicle with a streamlined design was able to reduce the generation of water vapor and decrease fluid resistance and its coefficient, and the vehicle can run farther during the water-entry process.

Calcium chloride seed priming: A dual-action strategy for enhancing Cyrtorhinus lividipennis attraction and deterring brown planthopper infestations in rice - Zhong-Yan Zhu; Xiao-Bao Wu; Jia-jia An; Qian-Qian Deng; Jun Wang; Li-Na Chen; Mao Ye (Crop Protection, 2024)

Season-dependent climate sensitivity of the surface runoff of major rivers in Changbai Mountain - Xinran Li; Hong S. He; Na Li; Heyuan Yu; Shengwei Zong; Zhengfang Wu; Haibo Du (Journal of Hydrology, 2024)

Comparative analysis of anaerobic degumming effects on different bast fibers from the angle of enzyme activity and microbial community structure - Yiting Qin; Xuehui Xie; Haonan Mo; Yuling Li; Xiaoguang Chen; Yanxue Ma; Zhuoyu Zhao; Hangmi Zheng; Yao Sun; Dongyang Li; Ziyi Wu; Na Liu; et al. (Journal of Cleaner Production, 2024)

Calcium regulates nitrogen removal in constructed wetlands: The interactions between dissolved organic matter and microbial response - Dongdong Yao; Huijun Xie; Yunkai Li; Shiwen Zhang; Na Dai; Zhen Hu; Haiming Wu; Shuang Liang; Jian Zhang (Chemical Engineering Journal, 2024)

Brain Immune Cell Infiltration and Serum Metabolomic Characteristics Reveal that Lauric Acid Promotes Immune Cell Infiltration in Brain and Streptococcus suis Meningitis in Mice - Xuan Jiang; Fengyang Li; Jikun Mei; Tong Wu; Junhui Zhu; Ziheng Li; Zengshuai Wu; Hexiang Jiang; Na Li; Liancheng Lei (Molecular Neurobiology, 2024)

NUS1 Variants Cause Lennox-Gastaut Syndrome Related to Unfolded Protein Reaction Activation - Nan-Xiang Shen; Xiao-Chong Qu; Jing Yu; Cui-Xia Fan; Fu-Li Min; Ling-Ying Li; Ming-Rui Zhang; Bing-Mei Li; Jie Wang; Na He; Wei-Ping Liao; Yi-Wu Shi; et al. (Molecular Neurobiology, 2024)

Fine particulate matter components associated with exacerbated depressive symptoms among middle-aged and older adults in China - Haisheng Wu; Jiaqi Liu; Erica Conway; Na Zhan; Lishuang Zheng; Shengzhi Sun; Jinhui Li (Science of The Total Environment, 2024)

Molecular dynamics-based targeted adsorption of hazardous substances from rubberized asphalt VOCs by UiO-67 - Yang Lv; Shaopeng Wu; Haiqin Xu; Quantao Liu; Na Li; Chao Yang; Serji Amirkhanian (Journal of Cleaner Production, 2024)

Boosting solvent resistance and structure stability of degradable polyester through extended-chain crystal structure: A preliminary case of oil/water separation membrane - Jia-Yao Chen; Na Li; Siyang Wang; Tian-Yu Wu; Xiaoyu Meng; Hai-Mu Ye (Journal of Environmental Chemical Engineering, 2024)

Selective catalytic reduction of NO by CO over spinel CuFe2O4 catalyst: The vital role of oxygen vacancies - Chenyang Wu; Na Li; Yuqing Pan; Xiaole Chen; Lehang Chen; Qulan Zhou; Zhong Huang (Journal of Environmental Chemical Engineering, 2024)

Molecular mechanism of phytochemical cinnamic acid/cinnamaldehyde from the spice cinnamon binding to bovine haemoglobin - Lijuan Chen; Jingtao Pang; Yilin Li; Na Gan; Qingling Wang; Di Wu (Food Bioscience, 2024)

Selective and antibacterial zinc phosphonate framework system for superior marine uranium harvesting - Nan Li; Shideng Yuan; Ruidian Su; Jiakun Wu; Na Shi; Lei Wang; Zhining Wang (Desalination, 2024)

Research Advances in Neuroblast Migration in Traumatic Brain Injury - Na Wu; Wenlang Li; Qiang Chen; Meng Chen; Siyuan Chen; Chongjie Cheng; Yimin Xie (Molecular Neurobiology, 2024)
Neuroblasts were first derived from the adult mammalian brains in the 1990s by Reynolds et al. Since then, persistent neurogenesis in the subgranular zone (SGZ) of the hippocampus and subventricular zone (SVZ) has gradually been recognized. To date, reviews on neuroblast migration have largely investigated glial cells and molecular signaling mechanisms, while the relationship between vasculature and cell migration remains a mystery. Thus, this paper underlines the partial biological features of neuroblast migration and unravels the significance and mechanisms of the vasculature in the process to further clarify theoretically the neural repair mechanism after brain injury. Neuroblast migration presents three modes according to the characteristics of cells that act as scaffolds during the migration process: gliophilic migration, neurophilic migration, and vasophilic migration. Many signaling molecules, including brain-derived neurotrophic factor (BDNF), stromal cell-derived factor 1 (SDF-1), vascular endothelial growth factor (VEGF), and angiopoietin-1 (Ang-1), affect vasophilic migration, synergistically regulating the migration of neuroblasts to target areas along blood vessels. However, the precise role of blood vessels in the migration of neuroblasts needs to be further explored. The in-depth study of neuroblast migration will most probably provide theoretical basis and breakthrough for the clinical treatment of brain injury diseases. Graphical Abstract

Resveratrol suppresses liver cancer progression by downregulating AKR1C3: targeting HCC with HSA nanomaterial as a carrier to enhance therapeutic efficacy - Ying Wang; Longxiang Su; Zhansheng Hu; Shuang Peng; Na Li; Haiyan Fu; Baoquan Wang; Huiping Wu (Apoptosis, 2024)

Benzo(a)pyrene promotes the malignant progression of malignant-transformed BEAS-2B cells by regulating YTH N6-methyladenosine RNA binding protein 1 to inhibit ferroptosis - Na Wang; Hong-qiang Chen; Yong Zeng; Yu Shi; Zhe Zhang; Jiang-ying Li; Shi-meng Zhou; Ya-wen Li; Shuang-wu Deng; Xue Han; Zi-yuan Zhou; Mao-lin Yao; et al. (Toxicology, 2024)

In vitro generation of trophoblast like stem cells from goat pluripotent stem cells - Qin Na; Siyu Zhang; Peng Shao; Yu Jia; Yanqiu Wang; Mengyi Wei; Yanglin Chen; Chen Chen; Lixia Zhao; Zixin Wang; Yongli Song; Baojiang Wu; et al. (Theriogenology, 2024)

Estimation of ammonia emissions from rice fields under different N inputs in China - Na Li; Xiaoyu Ni; Ye Yang; Yuejin Wu; Weizheng Shu; Wenge Wu; Yang Yang (Resources, Conservation and Recycling, 2024)

Integrative multi-omics analysis reveals the underlying toxicological mechanisms of enrofloxacin on the growth of wheat seedling roots - Xiaojun Wu; Xiangdong Chen; Dazhong Zhang; Xigui Hu; Weihua Ding; Yuquan Wang; Gan Li; Na Dong; Haiyan Hu; Tiezhu Hu; Zhengang Ru (Journal of Hazardous Materials, 2024)

Separation of ovomucin from duck egg white and its “acid-tight /alkali-loose” self-supporting gel properties under different pH - Yao Yao; Yucheng Zhong; Han Li; Tiantian Liu; Na Wu; Shuping Chen; Lilan Xu; Yan Zhao; Yonggang Tu (Food Hydrocolloids, 2024)

Relationship between resistivity and physical properties of seafloor sediments in the hydrate production test area of the South China Sea - Zhiwen Sun; Yiping Miao; Zhihan Fan; Xiaoshuai Song; Liang Xue; Na Zhu; Xianming Zhu; Xiaomeng Li; Yue Qiao; Zhongqiang Sun; Kai Li; Yanlong Li; et al. (Marine Georesources & Geotechnology, 2024)

Plasma Deoxycholic Acid Levels are Associated with Hemodynamic and Clinical Outcomes in Acute Pulmonary Embolism Patients - Na Sun; Yi-Qiang Chen; Yan-Sheng Chen; Lei Gao; Run-Wei Deng; Jing Huang; You-Li Fan; Xuan Gao; Bin-Feng Sun; Na-Na Dong; Bo Yu; Xia Gu; et al. (Cardiovascular Toxicology, 2024)

A DEM upscaling method with integrating valley lines based on HASM - Mingwei Zhao; Xiaoxiao Ju; Na Zhao; Chun Wang; Yan Xu; Xiaoran Wu; Weitao Li (Frontiers of Earth Science, 2024)

Short-term response of soil fungal community composition and trophic mode to winter mulch management in Lei bamboo (Phyllostachys praecox) forests - Linping Zhang; Nancai Pei; Fei Wu; Na Wu; Zuyao Li; Yuxuan Huang; Mingxi Tan; Ying Yang (Applied Soil Ecology, 2024)

Performance of pharmaceutical products removal in a bioelectrochemical system at low temperatures and changes in microbial communities and antibiotic resistance genes - Mei Wu; Nuerla Ailijiang; Na Li; Abudoushalamu Zaimire; Hailiang Chen; Chaoyue He; Yiming Zhang (Environmental Science and Pollution Research, 2024)

Conformational transformation of activator strand directly regulates CRISPR/Cas12a system activity for live cell sensing of multiple biomolecules - Qing-Nan Li; Dong-Xia Wang; Zhi-Qi Dai; Shun-Li Wu; Gui-Mei Han; Sha Lu; Li-Na Zhu; Hong-Xin Jiang; De-Ming Kong (Chemical Engineering Journal, 2024)

Macaque Brainnetome Atlas: A multifaceted brain map with parcellation, connection, and histology - Yuheng Lu; Yue Cui; Long Cao; Zhenwei Dong; Luqi Cheng; Wen Wu; Changshuo Wang; Xinyi Liu; Youtong Liu; Baogui Zhang; Deying Li; Bokai Zhao; et al. (Science Bulletin, 2024)

Simultaneous determination of advanced glycation end products and heterocyclic amines in roast/grilled meat by UPLC-MS/MS - Mingyu Li; Chunjiang Zhang; Zhenyu Wang; Na Liu; Ruiyun Wu; Jiajing Han; Wenhan Wei; Christophe Blecker; Dequan Zhang (Food Chemistry, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Neural network based on convolution and self-attention fusion mechanism for plant leaves disease recognition - Yun Zhao; Yang Li; Na Wu; Xing Xu (Crop Protection, 2024)

Genomic and transcriptomic analysis reveals the genetic diversity and adaptive signatures of Maduo sheep - Li-Na Chang; Xue Gao; Shi-Xin Wu; Rui-Dong Wan; Zhan-Xing Yang; Hai-Mei Zhao; Ke Zhang; Xin-Quan Zhao; You-Gui Fang; Gong-Xue Jia (Small Ruminant Research, 2024)

Anti-inflammatory activity of organic acids from the seeds of Phaseolus lunatus L. - Kun Li; Jin-hui Bian; Heng Wu; Ya-lan Wang; Yun-jia Feng; Jia Nie; Na Chen; Han Yu; Wan Li; Yu-zhu Tan; Guang-hua Lu (Phytochemistry Letters, 2024)

Carbazole-Based branched Poly(Aryl Piperidinium) membranes for Ultra-Stable anion exchange membrane fuel cells - Jiayao Yang; Jialin Zhao; Na Li; Yijia Lei; Jingyi Wu; Jian Gao; Shiyao Sun; Kuirong Feng; Yan Wang; Zhe Wang (Chemical Engineering Journal, 2024)

Delineating cathodic extracellular electron transfer pathways in microbial electrosynthesis: Modulation of polarized potential and Pt@C addition - Yue Wang; Siyang Yu; Xue Zheng; Xiaobing Wu; Ying Pu; Gaoying Wu; Na Chu; Xiaohong He; Daping Li; Raymond Jianxiong Zeng; Yong Jiang (Bioresource Technology, 2024)

Investigating phosphorus adsorption characteristics of sediment in a river reach receiving municipal tailwater: a response surface methodology - Ruzhong Li; Congxin Huang; Dongpo Na; Xiaolong Wu (Journal of Soils and Sediments, 2024)

Assessment of the comprehensive carrying capacity of the central plains urban agglomeration in the Yellow River Basin, China - Shuhan Yang; Ruyin Long; Hong Chen; Meifen Wu; Qianwen Li; Yujie Wang; Xinru Wang; Jingwen Na (Environment, Development and Sustainability, 2024)

Sublethal effect and detoxifying metabolism of metaflumizone and indoxacarb on the fall armyworm, Spodoptera frugiperda - Li Zhang; Hui-Zi Wu; Pei-Yun He; Hai-Qun Cao; Wan-Na Zhang; Ying-Chuan Peng; Cheng-Wang Sheng (Pesticide Biochemistry and Physiology, 2024)

Novel oleophilic tracer-slow-released proppant for monitoring the oil production contribution - Zhibo Gong; Na Li; Wei Kang; Mei Qin; Yan Wu; Xu Liu (Fuel, 2024)

Superior room-temperature efficacy of selective catalytic reduction of NO by CO utilizing metal-modified Fe2O3 catalysts - Yuqing Pan; Na Li; Chenyang Wu; Qulan Zhou; Ke Li; Shuzhou Li (Chemical Engineering Journal, 2024)

Morusin inhibits breast cancer-induced osteolysis by decreasing phosphatidylinositol 3-kinase (PI3K)-mTOR signalling - Long Zhang; Weibin Li; Xiaohui Chen; Dongmin Cao; Siyuan You; Fan Shi; Zhengqiong Luo; Hongyu Li; Xiangchen Zeng; Yabin Song; Na Li; Yoshie Akimoto; et al. (Chemico-Biological Interactions, 2024)

Genome constitution and evolution of Elymus atratus (Poaceae: Triticeae) inferred from cytogenetic and phylogenetic analysis - Lu Tan; Dan-Dan Wu; Chang-Bing Zhang; Yi-Ran Cheng; Li-Na Sha; Xing Fan; Hou-Yang Kang; Yi Wang; Hai-Qin Zhang; Marcial Escudero; Yong-Hong Zhou (Genes & Genomics, 2024)

Spatial-temporal constraints for surface soil moisture mapping using Sentinel-1 and Sentinel-2 data over agricultural regions - ZHOU Ya'nan; WANG Binyao; ZHU Weiwei; FENG Li; HE Qisheng; ZHANG Xin; WU Tianjun; YAN Na'na (Computers and Electronics in Agriculture, 2024)

A new strategy to stabilize the heavy metals in carbonized MSWI-fly ash using an acid-resistant oligomeric dithiocarbamate chelator - Bojun Li; Xuejun Guo; Xiangyuan Zhang; Siwen Leng; Na Ma; Xiaoqiong Wu (Journal of Hazardous Materials, 2024)

Simulation of inhibition and targeted adsorption of rubberized asphalt VOCs by UiO-66 based on molecular dynamics - Yang Lv; Shaopeng Wu; Haiqin Xu; Na Li; Quantao Liu; Huan Wang; Yingxue Zou; Qi Jiang; Serji Amirkhanian (Journal of Cleaner Production, 2024)

Molecular mechanism of efficient degradation of TPM dyes by Serratia species WKD at high temperature - Yi Wei; Xin-Jiao Dong; Gang Li; Huan Wu; Lin-Na Du; Jia-Cheng Zhou; Jun Zhang; Yan-Ping Xiao; Yue-Mei Shang; Hong-Xia Liu (International Biodeterioration & Biodegradation, 2024)

Effect of konjac glucomannan on gelling and digestive properties of myofibrillar protein in Litopenaeus vannamei based on molecular docking - Deyang Li; Na Li; Yefan Wang; Kexin Zhang; Zhifeng Tan; Huilin Liu; Xiaoyang Liu; Qiong Wu; Dayong Zhou (Food Hydrocolloids, 2024)

Effect of mixture microstructure/compatibility on the properties of type-A gelatin-dextran edible films - Ling Wu; Bo Cui; Die Dong; Zhengzong Wu; Jianpeng Li; Lu Lu; Na Wang; Katsuyoshi Nishinari; Meng Zhao (Carbohydrate Polymers, 2024)

Are you a happy traveler? Exploring ridesourcing travelers' satisfaction and subjective well-being - Hongyun Si; Na Li; Long Cheng; Guangdong Wu; Jonas De Vos (Transportation Research Part D: Transport and Environment, 2024)

Study on small strain characteristics and microscopic mechanism of rice husk ash modified lime soil - Na Li; Shimeng Yu; Erlu Wu; Xinjiang Song; Ping Jiang; Haibo Xu; Wei Wang (Transportation Geotechnics, 2024)

Facile synthesis of hydroxylated triazine-based magnetic microporous organic network for ultrahigh adsorption of phenylurea herbicides: An experimental and density-functional theory study - Lu Liu; Lu-Qin Qiao; Feng Liu; Qian-Yun Sun; Yan-Fang Zhao; Xiao-Li Wang; Na Li; Hai-Long Jiang; Xiang-Feng Chen; Ming-Lin Wang; Yong-Ning Wu; Ru-Song Zhao (Journal of Hazardous Materials, 2024)

Pigmentiphaga kullae CHJ604 improved the growth of tobacco by degrading allelochemicals and xenobiotics in continuous cropping obstacles - Jia-Xi Xiong; Ling-Shan Du; Na-Na Li; Xiu-Ting Wu; Yang Xiang; Sha Li; Lei Zou; Dongqi Liu; Duo Huang; Ze Feng Xie; Ying Wang; Jinhua Li; et al. (Journal of Hazardous Materials, 2024)

S-scheme heterojunction and heterovalent ion doping synergistically promote the visible light photocatalytic performance of hierarchical nanoflowers - Hongwei Wu; Jie Li; Yuanli Li; Wei Feng; Xiaoyan Zhong; Sili Liu; Haifeng Liu; Na Li; Ruishi Xie (Journal of Cleaner Production, 2024)

Norepinephrine-induced hydrophilic Pd aerogels with photothermal-boosted multienzyme-like activity for chemodynamic therapy of MRSA infections - Minghui Wang; Na Li; Nanyun Lin; Yingying Wu; Wei Zhou; Ximei Sun; Peixian Wu; Qian Fu; Wenjie Wang; Zheng Liu; Shuiyuan He; Mengyu Zhou; et al. (Chemical Engineering Journal, 2024)

Development of lactoferrin-coated multifunctional copolymer micelles to cross the blood-brain barrier - Na Ouyang; Chunhua Yang; Xia Li; Zhenting Zheng; Yuanyuan Xu; Yinan Wang; Wei Xiong; Haiqiang Wu (Drug Delivery and Translational Research, 2024)

Biological roles of soil microbial consortium on promoting safe crop production in heavy metal(loid) contaminated soil: A systematic review - Na Wang; Xiangxiang Wang; Li Chen; Hongjie Liu; Yanfang Wu; Min Huang; Linchuan Fang (Science of The Total Environment, 2024)

Performance and mechanism of SMX removal by an electrolysis-integrated ecological floating bed at low temperatures: A new perspective of plant activity, iron plaque, and microbial functions - Ying Liu; Maozhen Han; Fengmin Li; Na Zhang; Shaoyong Lu; Xiaohui Liu; Fengchang Wu (Journal of Hazardous Materials, 2024)

The enhanced visible-light-driven porous O/P-C3N4 for persulfate photoactivation: Enhanced removal of refractory pollutants and lignin valorization - Liquan Jing; Yuanguo Xu; Meng Xie; Chongchong Wu; Xia Du; Heng Zhao; Na Zhong; Huaming Li; Ian D. Gates; Jinguang Hu (Chemical Engineering Journal, 2024)

Biodegradation of vulcanized natural rubber by enriched bacterial consortia - Yangjian Cheng; Yanchen Wei; Hongliang Wu; Tingting Zhang; Shihua Li; Na Zhu; Qiyun Zhang; Wen Li (Chemical Engineering Journal, 2024)

Recovery and reuse of spent lithium-ion batteries as catalysts for low-temperature NH3-SCR - Na Wu; Mengtao Li; Qiao Zhang; Gang Xue; Yaping Wang; Cairong Gong (Chemical Engineering Journal, 2024)

3D network of zinc powder woven into fibre filaments for dendrite-free zinc battery anodes - Lin Sha; Bin-Bin Sui; Peng-Fei Wang; Zhe Gong; Yu-Hang Zhang; Yu-Han Wu; Li-Na Zhao; Jun-Jie Tang; Fa-Nian Shi (Chemical Engineering Journal, 2024)

α-Glucan derivatives as selective blockers of aldolase A: Computer-aided structure optimization and the effects on HCC - Qian-Han Xiao; Ze-Zhi Li; Li Ren; Shu-Yao Wang; Xiao-Qiang Li; Hong-Xin Bai; Rui-Zhi Qiao; Na Tang; Wen-Juan Liu; Jing-Mei Wang; Guang-Yuan Ma; Dian-Chao Dong; et al. (Carbohydrate Polymers, 2024)

Nitrogen-mediated distinct rhizosphere soil microbes contribute to Sorghum bicolor (L.) Moench and Solanum nigrum L. for phytoremediation of cadmium-polluted soil - Jiawen Wu; Na Zhao; Xiaoxiao Li; Pan Zhang; Ting Li; Yuan Lu (Plant and Soil, 2024)

Gemfibrozil Alleviates Cognitive Impairment by Inhibiting Ferroptosis of Astrocytes via Restoring the Iron Metabolism and Promoting Antioxidant Capacity in Type 2 Diabetes - Nan Wang; Yujing Zhao; Meiyan Wu; Na Li; Chaoying Yan; Hongyan Guo; Qiao Li; Qing Li; Qiang Wang (Molecular Neurobiology, 2024)

Intravenous immunoglobulin for treatment of hospitalized COVID-19 patients: an evidence mapping and meta-analysis - Mei-xuan Li; Yan-fei Li; Xin Xing; Jun-qiang Niu; Liang Yao; Meng-ying Lu; Ke Guo; Mi-na Ma; Xiao-tian Wu; Ning Ma; Dan Li; Zi-jun Li; et al. (Inflammopharmacology, 2024)

O-acetyl-homoserine sulfhydrylase deficient Streptococcus suis serotype 2 strain SC19 becomes an avirulent strain and provides immune protection against homotype infection in mice - Tong Wu; Hexiang Jiang; Fengyang Li; Xuan Jiang; Jun Wang; Shaopeng Wei; Yi Sun; Yanyan Tian; Hong Chu; Yu Shi; Nan Zhang; Na Li; et al. (Veterinary Microbiology, 2024)

Oropharyngeal aspirated Ag/TiO2 nanohybrids: Transformation, distribution and toxicity - Xiaoquan Huang; Congcong Li; Tingting Wei; Na Liu; Yongshuai Yao; Zhihui Wang; Yuanyuan Hu; Qing Fang; Shujing Guan; Yuying Xue; Tianshu Wu; Ting Zhang; et al. (Science of The Total Environment, 2024)

Daily monitoring of Effective Green Area Index and Vegetation Chlorophyll Content from continuous acquisitions of a multi-band spectrometer over winter wheat - Wenjuan Li; Marie Weiss; Sylvain Jay; Shanshan Wei; Na Zhao; Alexis Comar; Raul Lopez-Lozano; Benoit De Solan; Qiangyi Yu; Wenbin Wu; Frédéric Baret (Remote Sensing of Environment, 2024)

Isolation and characterization of Bacillus cereus bacteriophage DZ1 and its application in foods - Zhichao Huang; Xiaoming Yuan; Zhenjun Zhu; Ying Feng; Na Li; Shubo Yu; Chun Li; Bo Chen; Shi Wu; Qihui Gu; Jumei Zhang; Juan Wang; et al. (Food Chemistry, 2024)

Tolerance mechanism of rice (Oryza sativa L.) seedings towards polycyclic aromatic hydrocarbons toxicity: The activation of SPX-mediated signal transduction to maintain P homeostasis - Jianjian Wu; Xinyue Liu; Fei Ge; Feng Li; Na Liu (Environmental Pollution, 2024)

Toll-Like Receptor 4 Deficiency Ameliorates Propofol-Induced Impairments of Cognitive Function and Synaptic Plasticity in Young Mice - Qiao-Ding Dai; Kang-Song Wu; Li-Ping Xu; Yan Zhang; Na Lin; Yao Jiang; Chong-Yu Shao; Li-Da Su (Molecular Neurobiology, 2024)

Single and mixture toxicity of cadmium and copper to swim bladder in early life stages of Japanese medaka (Oryzias latipes) - Xiaoqian Li; Yunyang Li; Melissa Chernick; David E. Hinton; Na Zheng; Chenyang Du; Wu Dong; Sujing Wang; Shengnan Hou (Environmental Geochemistry and Health, 2024)

Solution plasma synthesis of Pt-decorated Bi12O17Cl2 photocatalysts for efficient upcycling of plastics - Feiyan Wu; Changming Li; Yibo Dou; Jianchi Zhou; Tao Jiang; Yuechao Yao; Na Yeon Lee; Sung Yul Lim; Claus Hélix-Nielsen; Wenjing Zhang (Science of The Total Environment, 2023)

Three new flavones from the whole plants of Cassia auriculata Linn. and their antiviral activities - Rui-Feng Xiong; Jun-Na Zheng; Qing-Yang Wu; Ning Jiang; Yuan-Sheng He; Yong-Jun Zhang; Ben-Hui Li; Wei Li; Qiu-Fen Hu; Zhen-Yuan Xia; Yin-Ke Li (Phytochemistry Letters, 2023)

LuxS-deficiency reduces persistence of Cronobacter to low-moisture but contributes to virulence after rehydration - Na Ling; Zongyang Li; Yuhang Wang; Qingping Wu; Yingwang Ye; Jumei Zhang (Food Research International, 2023)

Effect of edible oil type on the formation of protein-bound Nε-(carboxymethyl)lysine in roasted pork patties - Na Li; Xuan Wu; Hailong Liu; Diandong Xie; Shuqi Hao; Zeyu Lu; Wei Quan; Jie Chen; Huaide Xu; Mei Li (Food Research International, 2023)

Tuning the oxidation level of GO to construct high performance crosslinked lamellar graphene oxide membrane for pervaporation desalination - Xiaowei Qian; Ziheng Wang; Jiawei Sun; Feixiang Zeng; Dongyun Wu; Zongli Xie; Na Li (Desalination, 2023)

Mettl13 protects against cardiac contractile dysfunction by negatively regulating C-Cbl-mediated ubiquitination of SERCA2a in ischemic heart failure - Shuting Yu; ZhiYong Sun; Xiuzhu Wang; Tiantian Ju; Changhao Wang; Yingqi Liu; Zhezhe Qu; KuiWu Liu; Zhongting Mei; Na Li; Meixi Lu; Fan Wu; et al. (Science China Life Sciences, 2023)

Protocol for Brain Magnetic Resonance Imaging and Extraction of Imaging-Derived Phenotypes from the China Phenobank Project - Chengyan Wang; Zhang Shi; Yan Li; Xueqin Xia; Xutong Kuang; Shufang Qian; Le Xue; Lizhen Lan; Yudan Wu; Na Zhang; Ji Tao; Xumei Hu; et al. (Phenomics, 2023)

Eif2s3y alleviated LPS-induced damage to mouse testis and maintained spermatogenesis by negatively regulating Adamts5 - Yunxiang Li; Wenping Wu; Wenjing Xu; Yuqi Wang; Shicheng Wan; Wenbo Chen; Donghui Yang; Mengfei Zhang; Xiaojie Wu; Xinchun Yang; Xiaomin Du; Congliang Wang; et al. (Theriogenology, 2023)

Ag/TiO2 nanohybrids induce fibrosis-related epithelial-mesenchymal transition in lung epithelial cells and the influences of silver content and silver particle size - Xiaoquan Huang; Congcong Li; Tingting Wei; Na Liu; Lingyue Zou; Changcun Bai; Yongshuai Yao; Zhihui Wang; Yuying Xue; Tianshu Wu; Ting Zhang; Meng Tang (Science of The Total Environment, 2023)

Selective extraction of uranium from seawater on amidoximated MXene/metal-organic framework architecture under an electric field - Nan Li; Li Yang; Ruidian Su; Na Shi; Jiakun Wu; Jia Zhao; Liping Wen; Zhining Wang (Desalination, 2023)

Amidoxime-functionalized cellulose nanofibers/MXene aerogel for electric field enhanced uranium extraction from seawater - Na Shi; Jiakun Wu; Xingyu Zhi; Nan Li; Zhining Wang (Chemical Engineering Journal, 2023)

Intermittent fasting and Alzheimer's disease—Targeting ketone bodies as a potential strategy for brain energy rescue - Yu- Cai Ye; Shi-Fan Chai; Xin-Ru Li; Mei-Na Wu; Hong-Yan Cai; Zhao-Jun Wang (Metabolic Brain Disease, 2023)

Investigation and prediction of the biotoxicity of Cu2+ to Chlorella vulgaris: modification of the biotic ligand model - Ming Kong; Zhiqiang Shi; Fei Liu; Na Song; Lizhen Liu; Rongfu Li; Yongming Wu; Huacheng Xu (Environmental Science and Pollution Research, 2023)

Inhibiting mechanisms of metal ion complexation on photogenerated reactive intermediates derived from dissolved black carbon - Yi-na Tu; Wei Tang; Weilin Wu; Huaying Liu; Xiangfen Cui; Senlin Tian; Yingjie Li; Weidong Jiao (Chemosphere, 2023)

Occurrence, source, and transfer fluxes of organophosphate esters in the South Pacific and Fildes Peninsula, Antarctic - Ruijing Li; Hui Gao; Chao Hou; Jie Fu; Tengda Shi; Zilan Wu; Shuaichen Jin; Ziwei Yao; Guangshui Na; Xindong Ma (Science of The Total Environment, 2023)

Ecological footprint model of heavy metal pollution in water environment based on the potential ecological risk index - Feng Yan; Na Li; Jingyi Wang; Hongliang Wu (Journal of Environmental Management, 2023)

Adsorption mechanism of methylene blue by magnesium salt-modified lignite-based adsorbents - Ruzhan Bai; Yan Feng; Lei Wu; Na Li; Quansheng Liu; Yingyue Teng; Runxia He; Keduan Zhi; Huacong Zhou; Xueyan Qi (Journal of Environmental Management, 2023)

Transcriptomic analysis reveals novel desiccation tolerance mechanism of Cronobacter based on type VI secretion system inhibition - Yang Wang; Na Ling; Rui Jiao; Xiyan Zhang; Yuwei Ren; Hui Li; Wenhua Zhao; Qingping Wu; Yingwang Ye (Food Research International, 2023)

Carboxyl-containing components delineation via feature-based molecular networking: A key to processing conditions of fermented soybean - Yuye Gao; Yu Fu; Na Li; Yuetong Jiang; Xiaojing Liu; Congcong Gao; Lishuang Wang; Jian-Lin Wu; Tingting Zhou (Food Chemistry, 2023)

Feature Extraction with Multi-fractal Spectrum for Coal and Gangue Recognition Based on Texture Energy Field - Na Li; Si-bo Wu; Zhen-hua Yu; Xing-yu Gong (Natural Resources Research, 2023)

Observed and projected changes in wet and dry spells for the major river basins in East Asia - Lirong Huang; Haibo Du; Yongcai Dang; Hong S. He; Lei Wang; Risu Na; Na Li; Zhengfang Wu (International Journal of Climatology, 2023)
Spatiotemporal changes in wet and dry spells had significantly contributed to climate‐related natural hazards in East Asia, especially in river basins undergoing warming. However, few studies have systematically analysed these changes for river basins at different latitudes. Herein, we investigated the observed and projected variations in wet and dry spells for East Asian river basins at different latitudes. We found that river basins at low latitudes (Yangtze and Pearl rivers) had obvious wet characteristics, whereas those at high latitudes (Amur and Yellow rivers) had obvious dry characteristics. In general, the river basins presented a ‘wet south but dry north’ spatial pattern. Long‐duration wet spells have been shown to be the primary contributor to total wet spells in low‐latitude river basins, while long‐duration dry spells have been found to be the primary contributor to total dry spells in high‐latitude river basins. Importantly, climate is changing from prolonged wet spells to short, intense wet spells in low‐latitude river basins, whereas the climate is changing from single, short dry spells to moderate, prolonged dry spells at high latitudes. These changes indicate a high probability of flash floods in river basins at low latitudes and a high probability of droughts at high latitudes. In the future, more temporally clustered heavy precipitation events and prolonged dry spells may lead to increasingly uneven precipitation in high‐latitude river basins and the Pearl River basin, especially under the higher shared socioeconomic pathway scenarios. In contrast, more frequent consecutive heavy precipitation events may aggravate the risk of flooding in the Yangtze River basin. These findings are expected to serve as a guide for flood and drought risk mitigation in East Asia under a warming climate.

Are the accessibility and facility environment of parks associated with mental health? A comparative analysis based on residential areas and workplaces - Hong Li; Na Ta; Bailang Yu; Jiayu Wu (Landscape and Urban Planning, 2023)

Environmental hazard reduction and anti-aging enhancement of steel slag powder-asphalt mastic based on TiO2@UiO-67 composites - Yang Lv; Shaopeng Wu; Na Li; Huan Wang; Peide Cui; Haiqin Xu; Yuechao Zhao; Chao Yang; Xinxing Zhou; Serji Amirkhanian (Journal of Cleaner Production, 2023)

Association between phthalate exposure and obesity risk: A meta-analysis of observational studies - Qian Wu; Gang Li; Chen-Yang Zhao; Xiao-Lin Na; Yun-Bo Zhang (Environmental Toxicology and Pharmacology, 2023)

Phase behavior tuning enable high-safety and crack-free Ni-rich layered cathode for lithium-ion battery - Na Liu; Lai Chen; Haoyu Wang; Jiayu Zhao; Fei Gao; Jing Liu; Jinyang Dong; Yun Lu; Ning Li; Qi Shi; Yuefeng Su; Feng Wu (Chemical Engineering Journal, 2023)

The addition of nano zero-valent iron during compost maturation effectively removes intracellular and extracellular antibiotic resistance genes by reducing the abundance of potential host bacteria - Shizheng Zhou; Hualing Li; Zhiyin Wu; Si Li; Zhen Cao; Baohua Ma; Yongde Zou; Na Zhang; Ziyu Liu; Yan Wang; Xindi Liao; Yinbao Wu (Bioresource Technology, 2023)

Spautin-1 Protects Against Mild TBI-Induced Anxiety-Like Behavior in Mice via Immunologically Silent Apoptosis - Hui-Tao Miao; Rong-Xin Song; Yue Xin; Lu-Ying Wang; Jin-Meng Lv; Na-Na Liu; Zhi-You Wu; Wei Zhang; Yan Li; Dong-Xue Zhang; Li-Min Zhang (NeuroMolecular Medicine, 2023)

HSP70 attenuates neuronal necroptosis through the HSP90α-RIPK3 pathway following neuronal trauma - Tao Chen; Yun-Na Tao; Yan Wu; Xu Ren; Yun-Fei Li; Yu-Hai Wang (Molecular Biology Reports, 2023)

Nexus between natural resource and economic development: How green innovation and financial inclusion create sustainable growth in BRICS region? - Na Li; Di Wu (Resources Policy, 2023)

Comprehensive analysis of lncRNA-mRNA regulatory network in Populus associated with xylem development - Na Sun; Yufen Bu; Xinyuan Wu; Xiaocen Ma; Haobo Yang; Liang Du; Xiaojuan Li; Jianwei Xiao; Jinxing Lin; Yanping Jing (Journal of Plant Physiology, 2023)

Constructing branch architectures on fly ash surfaces to immobilize iron tetracarboxy phthalocyanine for synergistic degradation of dye contaminants - Peng Zhang; Na Wei; Jinqiang Wu; Qingyuan Liu; Lianfeng Yang; Shixun Zu; Chunhui Liu; Yun Li; Dapeng Li; Suxiang Ge; Juntao Ma (Journal of Cleaner Production, 2023)

Doxycycline induces the rebound of three tetracycline resistance genes during maturation of laying hen manure composting by increasing the abundance of potential host bacteria - Qing Liu; Xin Wen; Xinhua Li; Shan Zhong; Zhen Cao; Xin Zhang; Baohua Ma; Yongde Zou; Na Zhang; Jiandui Mi; Yan Wang; Xindi Liao; et al. (Journal of Cleaner Production, 2023)

Dynamic Measurements of Cerebral Blood Flow Responses to Cortical Spreading Depolarization in the Murine Endovascular Perforation Subarachnoid Hemorrhage Model - Jin Yan; Wenlang Li; Chao Zhou; Na Wu; Xiaomin Yang; Qiuling Pan; Tao He; Yue Wu; Zongduo Guo; Yongzhi Xia; Xiaochuan Sun; Chongjie Cheng (Translational Stroke Research, 2023)

Scutellarin Acts via MAPKs Pathway to Promote M2 Polarization of Microglial Cells - Hao-Lun Chen; Li Yang; Xiao-Li-Na Zhang; Qiu-Ye Jia; Zhao-Da Duan; Juan-juan Li; Li-yang Zheng; Teng-teng Liu; Zhi Qi; Yun Yuan; Chun-Yun Wu (Molecular Neurobiology, 2023)

Impact of components number selection in truncated Gaussian mixture model and interval partition on wind speed probability distribution estimation - Jie Wu; Na Li (Science of The Total Environment, 2023)

Aroma correlation assisted volatilome coupled network analysis strategy to unveil main aroma-active volatiles of Rosa roxburghii - Ya-Hui Ge; Xue Li; Mingzheng Huang; Zhengxu Huang; Manman Wu; Baoqing Sun; Lishuang Wang; Jian-Lin Wu; Na Li (Food Research International, 2023)

The bound polyphenols of foxtail millet (Setaria italica) inner shell inhibit breast cancer by promoting lipid accumulation-induced autophagic death - Li-chao Zhang; Ya-ning Liu; Xiao-qin La; Shuai-tao Li; Li-na Wen; Ting Liu; Han-qing Li; Ai-ping Li; Haitao Wu; Chang-xin Wu; Zhuo-yu Li (Food and Chemical Toxicology, 2023)

Identification of contaminant source and hydraulic conductivity field based on an ILUES-SOM surrogate model - Na Zheng; Jinbing Liu; Xuemin Xia; Simin Gu; Yanhao Wu; Xianwen Li; Simin Jiang (Stochastic Environmental Research and Risk Assessment, 2023)

Unexpected association between ambient ozone and adult insomnia outpatient visits: A large-scale hospital-based study - Dawei Li; Lili Yang; Nan Wang; Yuegu Hu; Yumeng Zhou; Ning Du; Na Li; Xiaoling Liu; Chunyan Yao; Na Wu; Ying Xiang; Yafei Li; et al. (Chemosphere, 2023)

Efficient estimation of groundwater contaminant source and hydraulic conductivity by an ILUES framework combining GAN and CNN - Na Zheng; Simin Jiang; Xuemin Xia; Weiming Kong; Zhi Li; Simin Gu; Zijun Wu (Journal of Hydrology, 2023)

Multi-omics reveals Bifidobacterium longum CECT7894 alleviate food allergy by regulating the Sphingolipid metabolism pathway - Weiwei Cui; Qize Wen; Dengzhu Lurong; Yonghua Wu; Shenshen Gao; Jun Li; Na Li; Chundi Xu (Food Bioscience, 2023)

Room-temperature self-healing and recyclable polyurethane elastomers with high strength and superior robustness based on dynamic double-crosslinked structure - Yawen Xu; Shuai Zhou; Zihang Wu; Xinyu Yang; Na Li; Zhihui Qin; Tifeng Jiao (Chemical Engineering Journal, 2023)

Organic geochemical characteristics and organic matter accumulation of the Eocene lacustrine source rock in the Yingxi area, Western Qaidam Basin, China - Fan Yi; Haisheng Yi; Chuanlong Mu; Wenqiang Tang; Na Li; Yun Chen; Kangzhi Tian; Yuxiang Shi; Jinxuan Wu; Guoqing Xia (International Journal of Earth Sciences, 2023)

Temporal decline of genetic differentiation among populations of western flower thrips across an invaded range - Li-Na Sun; Li-Jun Cao; Jin-Cui Chen; Li-Jun Ma; Gui-Fen Zhang; San-An Wu; Ary Anthony Hoffmann; Shu-Jun Wei (Biological Invasions, 2023)

Whole-Genome Sequencing of a Multidrug-Resistant Strain: Delftia acidovorans B408 - Ke Li; Xue Liu; Wenlu Zuo; Na Wu (Biochemical Genetics, 2023)

Deyeuxia angustifolia upward migration and nitrogen deposition change soil microbial community structure in an alpine tundra - Na Li; Haibo Du; Mai-He Li; Risu Na; Renkai Dong; Hong S. He; Shengwei Zong; Lirong Huang; Zhengfang Wu (Soil Biology and Biochemistry, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

KNOX transcription factor VvHB63 affects grape seed development by interacting with protein VvHB06 - Jin Yao; Songlin Zhang; Na Wu; Xingmei Li; Bilal Ahmad; Jiuyun Wu; Rongrong Guo; Xiping Wang (Plant Science, 2023)

Earthworms and long-term straw management practices interactively affect soil carbon and nitrogen forms across soil depths - Maogang Xu; Xiaoyun Chen; Xishuai Liu; Jusong Huo; Yan Du; Na Li; Di Wu; Feng Hu; Manqiang Liu (European Journal of Soil Biology, 2023)

Rational design of molecular phototheranostic platform for NIR-II fluorescence imaging guided chemodynamic-photothermal combined therapy - Gui-long Wu; Bin Sun; Yuxuan He; Xiaofeng Tan; Qi Pan; Sha Yang; Na Li; Minghui Wang; Peixian Wu; Fen Liu; Hao Xiao; Li Tang; et al. (Chemical Engineering Journal, 2023)

MMPs, ADAMs and ADAMTSs are associated with mammalian sperm fate - Yunxiang Li; Yuguang Chen; Wenping Wu; Na Li; Jinlian Hua (Theriogenology, 2023)

Phytic acid is a new substitutable plant-derived antifungal agent for the seedling blight of Pinus sylvestris var. mongolica caused by Fusarium oxysporum - Na Li; Yu-Xuan Wu; Yun-Di Zhang; Shu-Ren Wang; Guo-Cai Zhang; Jing Yang (Pesticide Biochemistry and Physiology, 2023)

Highly selective CO2 electrocatalytic reduction on nickel single-atom catalyst in a high-temperature shockwave method - Jiawei Wang; Guoping Xiao; Na Gao; Jing Zhou; Mengna Xie; XianLong Du; Chuanqiang Wu; Shibo Xi; Tao Li; Jian-Qiang Wang (Fuel, 2023)

Comparison of two commercial methods with a UHPLC–MS/MS method for the determination of multiple mycotoxins in cereals - Ying-yue Zhang; Mei-juan Zhao; Chun-yao Liu; Kai Ma; Tian-yu Liu; Fei Chen; Li-na Wu; De-jun Hu; Guang-ping Lv (Food Chemistry, 2023)

Enhanced low-temperature behavior of selective catalytic reduction of NOx by CO on Fe-based catalyst with looping oxygen vacancy - Yuqing Pan; Na Li; Ke Li; Shiyuan Ran; Chenyang Wu; Qulan Zhou; Jiyuan Liu; Shuzhou Li (Chemical Engineering Journal, 2023)

Robust cellulose-based hydrogel marbles with excellent stability for gas sensing - Na Li; Hongying Wanyan; Shengchang Lu; He Xiao; Min Zhang; Kai Liu; Xiuliang Li; Bihui Du; Liulian Huang; Lihui Chen; Yonghao Ni; Hui Wu (Carbohydrate Polymers, 2023)

Obstructive sleep apnea-increased DEC1 regulates systemic inflammation and oxidative stress that promotes development of pulmonary arterial hypertension - Xiaoming Li; Xiang Zhang; Xiaozhi Hou; Xin Bing; Fangyuan Zhu; Xinhao Wu; Na Guo; Hui Zhao; Fenglei Xu; Ming Xia (Apoptosis, 2023)

Cobalt nanoparticles induce mitochondrial damage and β-amyloid toxicity via the generation of reactive oxygen species - Jingrong Chen; Cheng Chen; Na Wang; Chunyu Wang; Zhaohui Gong; Jingxian Du; Honglin Lai; Xinpei Lin; Wei Wang; Xiangyu Chang; Michael Aschner; Zhenkun Guo; et al. (NeuroToxicology, 2023)

Polarity-extended composition profiling via LC-MS-based metabolomics approaches: A key to functional investigation of Citrus aurantium L - Wen Miao; Xiaojing Liu; Na Li; Xiqing Bian; Yiran Zhao; Jing He; Tingting Zhou; Jian-Lin Wu (Food Chemistry, 2023)

Discovery of novel ascorbic acid derivatives and other metabolites in fruit of Rosa roxburghii Tratt through untargeted metabolomics and feature-based molecular networking - Yaqi Zhang; Xiqing Bian; Guanyu Yan; Baoqing Sun; Wen Miao; Mingzheng Huang; Na Li; Jian-Lin Wu (Food Chemistry, 2023)

The real-time detection of acupuncture-induced extracellular ATP mobilization in acupoints and exploration of its role in acupuncture analgesia - Wei-Min Zuo; Yu-Jia Li; Kai-Yu Cui; Dan Shen; Di Zhang; Ya-Wen Zheng; Meng Huang; Yong Wu; Xue-Yong Shen; Li-Na Wang; Guang-Hong Ding (Purinergic Signalling, 2023)

Analysis of PAT1 subfamily members in the GRAS family of upland cotton and functional characterization of GhSCL13-2A in Verticillium dahliae resistance - Chen Chen; Li-Li Lu; Shu-Ya Ma; Yan-Peng Zhao; Na Wu; Wen-Jie Li; Li Ma; Xian-Hui Kong; Zong-Ming Xie; Yu-Xia Hou (Plant Cell Reports, 2023)

Isolation and evaluation of antioxidants from Arisaema heterophyllum tubers - Na Sun; Huanhuan Yang; Miao Zhou; Yanyan Hou; Xinru Wu; Wenqian Li; Yifang Zhang; Jinge Sun; Xin Xiong; Jihong Huang; Penghua Shu (Phytochemistry Letters, 2023)

Magnetic metal–organic frameworks as adsorbents for the detection of azo pigments in food matrices - Lei Cheng; Rong Huang; Qiang Cao; Na Liu; Peiyi Li; Mengmeng Sun; Haiyang Qin; Lidong Wu (Food Chemistry, 2023)

Analysis of microbial community and its correlation with flavor compounds during Congee fermentation - Yang Yang; You Na Wu; Li Ge Er Ce; Xi Ge Bu Ren Ge; Quan Shuang; Feng Mei Zhang (Food Bioscience, 2023)

Supramolecular peptide hydrogel doped with nanoparticles for local siRNA delivery and diabetic wound healing - Liangyan Wu; Yanbo Chen; Gang Zeng; Na Mao; Na Li; Lanlan Li; Xiaoding Xu; Li Yan (Chemical Engineering Journal, 2023)

Liquid metal/CNTs hydrogel-based transparent strain sensor for wireless health monitoring of aquatic animals - Mengmeng Sun; Peiyi Li; Haiyang Qin; Na Liu; Hude Ma; Zhilin Zhang; Junye Li; Baoyang Lu; Xiaofang Pan; Lidong Wu (Chemical Engineering Journal, 2023)

IL-17A promotes endothelial cell senescence by up-regulating the expression of FTO through activating JNK signal pathway - Na Li; Runan Luo; Wenlong Zhang; Yu Wu; Chaojie Hu; Manli Liu; Diya Jiang; Ziran Jiang; Xinxin Zhao; Yiping Wang; Qing Li (Biogerontology, 2023)

Early identification of strawberry leaves disease utilizing hyperspectral imaging combing with spectral features, multiple vegetation indices and textural features - Gangshan Wu; Yinlong Fang; Qiyou Jiang; Ming Cui; Na Li; Yunmeng Ou; Zhihua Diao; Baohua Zhang (Computers and Electronics in Agriculture, 2023)

Structural insight into the constitutive activity of human orphan receptor GPR12 - Hao Li; Jinyi Zhang; Yanan Yu; Feng Luo; Lijie Wu; Junlin Liu; Na Chen; Zhijie Liu; Tian Hua (Science Bulletin, 2023)

Performance and VOCs emission inhibition of environmentally friendly rubber modified asphalt with UiO-66 MOFs - Yang Lv; Shaopeng Wu; Na Li; Peide Cui; Huan Wang; Serji Amirkhanian; Zenggang Zhao (Journal of Cleaner Production, 2023)

Enhanced silicate remediation in cadmium-contaminated alkaline soil: Amorphous structure improves adsorption performance - Lulu Long; Na Huang; Xin Liu; Li Gong; Min Xu; Shirong Zhang; Chao Chen; Jun Wu; Gang Yang (Journal of Environmental Management, 2023)

Bioinspired green tea waste/graphene aerogel for solar-enhanced uranium extraction from seawater - Nan Li; Jiakun Wu; Ruidian Su; Na Zhang; Jia Zhao; Zhining Wang (Desalination, 2023)

Self-healing properties of retrograded starch films with enzyme-treated waxy maize starch as healing agent - Li Guo; Na Yang; Wei Gao; Haiteng Tao; Bo Cui; Pengfei Liu; Feixue Zou; Lu Lu; Yishan Fang; Zhengzong Wu (Carbohydrate Polymers, 2023)

Does aspirin reduce the incidence, recurrence, and mortality of hepatocellular carcinoma? A GRADE-assessed systematic review and dose–response meta-analysis - Shaodi Ma; Guangbo Qu; Chenyu Sun; Haixia Liu; Yuemeng Jiang; Ning Li; Birong Wu; Juan Gao; Linya Feng; Peng Xie; Weihang Xia; Na Hyun Kim; et al. (European Journal of Clinical Pharmacology, 2023)

Effects of climate change and human activities on gross primary productivity in the Heihe River Basin, China - Xiaoliang Shi; Mengqi Shi; Na Zhang; Mengyue Wu; Hao Ding; Yi Li; Fei Chen (Environmental Science and Pollution Research, 2023)

Aaptamine derivatives with CDK2 inhibitory activities from the South China Sea sponge Aaptos suberitoides - Qian-Qian He; Yu-Qing Man; Kun-Lai Sun; Li-Juan Yang; Yan Wu; Jing Du; Wei-Wei Chen; Juan-Juan Dai; Na Ni; Shuang Miao; Kai-Kai Gong (Natural Product Research, 2022)

Effects of seawater acidification and solar ultraviolet radiation on photosynthetic performances and biochemical compositions of Rhodosorus sp. SCSIO-45730 - Na Wang; Jinting Lv; Fangfang Yang; Tao Li; Hualian Wu; Chulin Li; Haiwei Pei; Houbo Wu; Wenzhou Xiang (Frontiers in Marine Science, 2022)
Ocean acidification (OA) caused by rising atmospheric CO 2 concentration and solar ultraviolet radiation (UVR) resulting from ozone depletion may affect marine organisms, but little is known regarding how unicellular Rhodosorus sp. SCSIO-45730, an excellent species resource containing various biological-active compounds, responds to OA and UVR. Therefore, we conducted a factorial coupling experiment to unravel the combined effects of OA and UVR on the growth, photosynthetic performances, biochemical compositions and enzyme activities of Rhodosorus sp. SCSIO-45730, which were exposed to two levels of CO 2 (LC, 400 μatm, current CO 2 level; HC, 1000 μatm, future CO 2 level) and three levels of UVR (photosynthetically active radiation (PAR), PAR plus UVA, PAR plus UVB) treatments in all combinations, respectively. Compared to LC treatment, HC stimulated the relative growth rate (RGR) due to higher optimum and effective quantum yields, photosynthetic efficiency, maximum electron transport rates and photosynthetic pigments contents regardless of UVR. However, the presence of UVA had no significant effect but UVB markedly reduced the RGR. Additionally, higher carbohydrate content and lower protein and lipid contents were observed when Rhodosorus sp. SCSIO-45730 was cultured under HC due to the ample HCO 3 − applications and active stimulation of metabolic enzymes of carbonic anhydrase and nitrate reductase, thus resulting in higher TC/TN. OA also triggered the production of reactive oxygen species (ROS), and the increase of ROS coincided approximately with superoxide dismutase and catalase activities, as well as phenols contents. However, UVR induced photochemical inhibition and damaged macromolecules, making algal cells need more energy for self-protection. Generally, these results revealed that OA counteracted UVR-related inhibition on Rhodosorus sp. SCSIO-45730, adding our understanding of the red algae responding to future global climate changes.

Low-Level Environmental Per- and Polyfluoroalkyl Substances and Preterm Birth: A Nested Case–Control Study Among a Uyghur Population in Northwestern China - Bo-Yi Yang; Jianhua Wu; Xilong Niu; Chuanjiang He; Michael S. Bloom; Maihefuzaimu Abudoukade; Mairiyemu Abulizi; Aimin Xu; Beibei Li; Li Li; Xuemei Zhong; Qi-Zhen Wu; et al. (Exposure and Health, 2022)

Higher pH is associated with enhanced co‐occurrence network complexity, stability and nutrient cycling functions in the rice rhizosphere microbiome - Yaping Guo; Bin Song; Anqi Li; Qi Wu; Haili Huang; Na Li; Ying Yang; Jonathan Miles Adams; Lin Yang (Environmental Microbiology, 2022)
The rice rhizosphere microbiota is crucial for crop yields and nutrient use efficiency. However, little is known about how co‐occurrence patterns, keystone taxa and functional gene assemblages relate to soil pH in the rice rhizosphere soils. Using shotgun metagenome analysis, the rice rhizosphere microbiome was investigated across 28 rice fields in east‐central China. At higher pH sites, the taxonomic co‐occurrence network of rhizosphere soils was more complex and compact, as defined by higher average degree, graph density and complexity. Network stability was greatest at medium pH (6.5

In-situ photoreduction strategy for synthesis of silver nanoparticle-loaded PVDF ultrafiltration membrane with high antibacterial performance and stability - Shanshan Dong; Helin Hua; Xin Wu; Xuhui Mao; Na Li; Xinping Zhang; Kun Wang; Shengyun Yang (Environmental Science and Pollution Research, 2022)

New polymerized sesquiterpene lactones from Ainsliaea yunnanensis and their activity evaluation - Na Zhou; Jin-Jie Li; Yong Wu; Ze-Yu Wang; Xin Wang; Zhi-Peng Yin; Xin-Peng Wang; Yi-Ran Liu; Xiao-Ya Shang (Natural Product Research, 2022)

Maternal exposure to cooking oil fumes during pregnancy and autistic‐like behaviors in Chinese preschoolers - Jian-Hui Yang; Esben Strodl; Chuan-An Wu; Xiang-Yu Hou; Xiao-Na Yin; Guo-Min Wen; Deng-Li Sun; Dan-Xia Xian; Jing-Yi Chen; Ying-Jie Chen; Jing Chen; Wei-Qing Chen (Environmental Science and Pollution Research, 2022)

Increased serum anti-CYP2E1 IgG autoantibody levels may be involved in the pathogenesis of occupational trichloroethylene hypersensitivity syndrome: a case–control study - Tamie Nakajima; Hailan Wang; Yuan Yuan; Yuki Ito; Hisao Naito; Yoshiyuki Kawamoto; Kozue Takeda; Kiyoshi Sakai; Na Zhao; Hongling Li; Xinxiang Qiu; Lihua Xia; et al. (Archives of Toxicology, 2022)
Occupational exposure to trichloroethylene (TCE) causes a systemic skin disorder with hepatitis known as TCE hypersensitivity syndrome (TCE-HS). Human Leukocyte Antigen (HLA)-B*13:01 is its susceptibility factor; however, the immunological pathogenesis of TCE-HS remains unknown. We herein examined the hypothesis that autoantibodies to CYP2E1 are primarily involved in TCE-HS. A case–control study of 80 TCE-HS patients, 186 TCE-tolerant controls (TCE-TC), and 71 TCE-nonexposed controls (TCE-nonEC) was conducted to measure their serum anti-CYP2E1 antibody (IgG) levels. The effects of TCE exposure indices, such as 8-h time-weighted-average (TWA) airborne concentrations, urinary metabolite concentrations, and TCE usage duration; sex; smoking and drinking habits; and alanine aminotransferase (ALT) levels on the antibody levels were also analyzed in the two control groups. There were significant differences in anti-CYP2E1 antibody levels among the three groups: TCE-TC > TCE-HS patients > TCE-nonEC. Antibody levels were not different between HLA-B*13:01 carriers and noncarriers in TCE-HS patients and TCE-TC. The serum CYP2E1 measurement suggested increased immunocomplex levels only in patients with TCE-HS. Multiple regression analysis for the two control groups showed that the antibody levels were significantly higher by the TCE exposure. Women had higher antibody levels than men; however, smoking, drinking, and ALT levels did not affect the anti-CYP2E1 antibody levels. Anti-CYP2E1 antibodies were elevated at concentrations lower than the TWA concentration of 2.5 ppm for TCE exposure. Since HLA-B*13:01 polymorphism was not involved in the autoantibody levels, the possible mechanism underlying the pathogenesis of TCE-HS is that TCE exposure induces anti-CYP2E1 autoantibody production, and HLA-B*13:01 is involved in the development of TCE-HS.

Streptococcus humanilactis sp.nov., isolated from healthy nursing mother's breast milk - Xiaoqing Guo; Fei Han; Lin Cong; Yu Li; Yue Wu; Chen Liu; Jingfang Yang; Risu Na; Wenjun Liu (Archives of Microbiology, 2022)

Transcriptome Analysis of Greenfin Horse-Faced Filefish (Thamnaconus septentrionalis) Gills in Response to Amyloodinium ocellatum (AO) Infection - Li-Guo Yang; Yue Wang; Wen-Bin Xu; Bo Qin; Na Ying; Xue-Feng Song; Yan-Feng Yue; Xiao-Shan Wang; Bian-Bian Zhang; Yan-Qing Wu (Fishes, 2022)
The greenfin horse-faced filefish (Thamnaconus septentrionalis) is susceptible to recurrent Amyloodinium ocellatum (AO) infestation over the grow-out production cycle. This parasite breeds mainly on the gills, causing hypoxia in the fish body, and leading to many deaths. The host-parasite response drives a complex immune reaction, which is poorly understood. To generate a model for host-parasite interaction and the pathogenesis of AO in greenfin horse-faced filefish, an RNA-seq approach, differential gene expression, GO, and KEGG analyses were employed. Overall, 624 new genes and 2076 differentially expressed genes (DEGs) were detected, including 942 upregulated and 1134 downregulated genes in the gills. Compared with the control group, the expression of leptin a, GTPase IMAP family member 4, and NLR family CARD domain-containing protein 3 was significantly higher in the AO-infected group. Conversely, cell wall integrity and stress response component 1-like, and hepcidin-like were significantly downregulated in the gills of AO-infected fish. GO and KEGG enrichment analysis indicated that DEGs were significantly enriched in signaling pathways associated with viral protein interaction with cytokine and cytokine receptor and cytokine–cytokine receptor interaction. Collectively, this transcriptomic study provides novel molecular insights into the pathology caused by AO infestation and alternative theories for future research implementing strategies to control and manage AO.

Elder people can be more susceptible to the association between short-term ambient air pollution and sleep disorder outpatient visits: a time-series study - Yu-Meng Zhou; Shu-Jie An; Yi Cao; Chen Xu; Xiao-Ling Liu; Chun-Yan Yao; Xiang Li; Na Wu; Cheng-Ying Li; Long Wu; Ya-Fei Li; Ai-Ling Ji; et al. (Environmental Science and Pollution Research, 2022)

Ancylostoma ceylanicum Infection in a Miniature Schnauzer Dog Breed - Xu-Hui Lin; Hai-Ming Cai; Zhuan-Qiang Yan; Shen-Quan Liao; Min-Na Lv; Cai-Yan Wu; Juan Li; Jun-Jing Hu; Wen-Wan Xiao; Jian-Fei Zhang; Nan-Shan Qi; Ming-Fei Sun (Acta Parasitologica, 2022)

SbWRKY55 regulates sorghum response to saline environment by its dual role in abscisic acid signaling - Yushuang Song; Hongxiang Zheng; Yi Sui; Simin Li; Fenghui Wu; Xi Sun; Na Sui (Theoretical and Applied Genetics, 2022)

Non-peer-reviewed data, effect measures, and meta-regression analysis on proton pump inhibitor use and COVID-19 - Dan-Na Wu; Li-Rong Jiao; Guo-Fu Li; Guo Yu (European Journal of Clinical Pharmacology, 2022)

p-Nitrophenol contaminated soil remediation in a spray-type coaxial cylindrical dielectric barrier discharge plasma system - Nan Jiang; Ying Qu; Zheng Yu; Bangfa Peng; Jie Li; Kefeng Shang; Na Lu; Yan Wu (Environmental Science and Pollution Research, 2022)

Influence of joint angle on the instability failure characteristics and AE evolution law of underground caverns - Xiao Wang; Na Wu; Hong Li; Yatao Yan (European Journal of Environmental and Civil Engineering, 2022)

A superior allele of the wheat gene TaGL3.3-5B, selected in the breeding process, contributes to seed size and weight - Chaojie Wang; Lili Zhang; Yongdun Xie; Xiaofeng Guo; Yanfang Zhang; Yamin Zhang; Ahsan Irshad; Yuting Li; Huihui Qian; Doudou Jing; Guangyao Liu; Kaiming Wu; et al. (Theoretical and Applied Genetics, 2022)

Calycosin prevents IL-1β-induced articular chondrocyte damage in osteoarthritis through regulating the PI3K/AKT/FoxO1 pathway - Xiang Guo; Xiaoyu Pan; Jianhong Wu; Yuanzhou Li; Na Nie (In Vitro Cellular & Developmental Biology - Animal, 2022)

G-protein coupled receptor 34 regulates the proliferation and growth of LS174T cells through differential expression of PI3K subunits and PTEN - Bo Zuo; Na Wu; Shen Yang; Zhaohui Zhong; Mei Li; Xin Yu; Yulan Liu; Weidong Yu (Molecular Biology Reports, 2022)
Purpose G-protein coupled receptor (GPR 34) has been found to play important roles in some cancers and regulates the proliferation, apoptosis, and migration of these cancer cells. However, the mechanisms underlying how GPR34 functions to regulate growth and proliferation of colorectal cancer cells remains to be clarified. Methods We employed stable GPR34 knockdown LS174T cell models, GPR34 Mab blocking, a CCK-8 kit, and a colony formation assay to characterize the effect of GPR34 on the proliferation of LS174T in vitro and xenograft tumor growth in vivo. The mRNA level of GPR34 was detected by RT-PCR in tumor tissues and adjacent normal tissues from 34 CRC patients. Results Based on RT-PCR results, GPR34 exhibited high level in tumor samples compared with adjacent normal samples. Increased expression of GPR34 is more associated with poor prognosis of CRC as shown in The Cancer Genome Atlas (TCGA) dataset by Kaplan–Meier survival analysis. Furthermore, we showed that GPR34 knockdown inhibited the proliferation of LS174T colon cancer cells and related xenograft tumor growth. Searching for the distinct molecular mechanism, we identified several contributors to proliferation of LS174T colon cancer cells: PI3K subunits/PTEN, PDK1/AKT, and Src/Raf/Ras/ERK. GPR34 knockdown inhibited the proliferation of LS174T cells by upregulating expression of PTEN, and downregulating expression of PI3K subunits p110-beta. Conclusion Our findings provide direct evidence that GPR34 regulates the proliferation of LS174T cells and the growth of LS174T tumor xenografts by regulating different pathways. High expression of GPR34 mRNA could then be used to predict poor prognosis of CRC.

Associations of CXCL12 polymorphisms with clinicopathological features in breast cancer: a case-control study - Shuai Lin; Yi Zheng; Meng Wang; Linghui Zhou; Yuyao Zhu; Yujiao Deng; Ying Wu; Dai Zhang; Na Li; Huafeng Kang; Zhijun Dai (Molecular Biology Reports, 2022)
Background Previous studies suggested that CXCL12 was involved in the development, metastasis, and invasion of breast cancer, and genetic variants were associated with the diagnosis and prognosis of patients with breast cancer. The present study was aimed to assess the relationships between CXCL12 polymorphisms (rs1801157, rs2297630, and rs2839693) and susceptibility and clinicopathological features of breast cancer. Methods A case-control study was conducted in 434 breast cancer patients and 450 health controls. Student t -test and chi-square test were used to analyze the differences of age distribution and genotype frequencies between the two groups. Correlations between polymorphisms and clinical parameters were also assessed by chi-square test. The potential effects of the three polymorphisms on CXCL12 were investigated by the public database. Results A statistical association was found between CXCL12 rs1801157 polymorphism and breast cancer risk, possibility of metastasis, and estrogen receptor status. Patients with rs2839693 C/T or C/T-T/T genotypes were more likely to be progesterone receptor-negative. However, no associations of rs2297630 polymorphism with breast cancer risk or any clinicopathological characteristics were observed. In addition, rs2297630 affected the splicing quantitative trait loci of CXCL12 in the subcutaneous fat, rs2839693 polymorphism affected the splicing quantitative trait loci of CXCL12 in the human breast mammary tissues. Conclusions Those results indicated that CXCL12 polymorphisms might be potential diagnostic indicators, and more investigation is needed in the future.

VSIG4 Attenuates NLRP3 and Ameliorates Neuroinflammation via JAK2-STAT3-A20 Pathway after Intracerebral Hemorrhage in Mice - Na Ji; Lirong Wu; Hui Shi; Qianlu Li; Anyong Yu; Zhao Yang (Neurotoxicity Research, 2022)

Extraction optimization, physicochemical characterization, and antioxidant activity of polysaccharides from Rhodosorus sp. SCSIO-45730 - Na Wang; Lumei Dai; Zishuo Chen; Tao Li; Jiayi Wu; Houbo Wu; Hualian Wu; Wenzhou Xiang (Journal of Applied Phycology, 2022)

Dexmedetomidine targets miR-146a and participates in the progress of chronic obstructive pulmonary disease in vivo and in vitro - Na Li; Shuangfeng Li; Yehua Wu; Lu Xiong; Tiejun Li; Dandan Xing; Qiuchang Li; Duozhi Wu (Genes & Genomics, 2021)

Construction of a eukaryotic expression system with stable and secretory expression of mycobacterium tuberculosis 38 kDa protein - Huiying Chen; Zedian Chen; Na Bai; Renhe Yan; Mingyu Xu; Wangsheng Wu; Wenhan Liang; Hongwei Li; Yingying Mao (World Journal of Microbiology and Biotechnology, 2021)

Gastrodin Regulates the Notch Signaling Pathway and Sirt3 in Activated Microglia in Cerebral Hypoxic-Ischemia Neonatal Rats and in Activated BV-2 Microglia - Jing Guo; Xiao-Li-Na Zhang; Zhang-Rui Bao; Xue-Ke Yang; Ling-Shuang Li; Yu Zi; Fan Li; Chun-Yun Wu; Juan-Juan Li; Yun Yuan (NeuroMolecular Medicine, 2021)

Associations of acute exposure to airborne pollutants with COVID-19 infection: evidence from China - Bingqing Lu; Na Wu; Jiakui Jiang; Xiang Li (Environmental Science and Pollution Research, 2021)

Study of the mechanical performance of excavation under asymmetrical pressure and reinforcement measures - Wenchao Zhang; Na Wu; Pengjiao Jia; Xiaoqi Zhou; Hong Li; Guoguang Wang (Arabian Journal of Geosciences, 2021)

The NDR kinase–MOB complex FgCot1‐Mob2 regulates polarity and lipid metabolism in Fusarium graminearum - Na Liu; Jing Wang; Yingzi Yun; Jinli Wang; Chaoyun Xu; Siqi Wu; Luona Xu; Baohua Li; Ilana Kolodkin‐Gal; Dawood H. Dawood; Youfu Zhao; Zhonghua Ma; et al. (Environmental Microbiology, 2021)
Summary Members of the NDR (nuclear Dbf2‐related) protein‐kinase family are essential for cell differentiation and polarized morphogenesis. However, their functions in plant pathogenic fungi are not well understood. Here, we characterized the NDR kinase FgCot1 and its activator FgMob2 in Fusarium graminearum , a major pathogen causing Fusarium head blight (FHB) in wheat. FgCot1 and FgMob2 formed a NDR kinase–MOB protein complex. Localization assays using FgCot1‐GFP or FgMob2‐RFP constructs showed diverse subcellular localizations, including cytoplasm, septum, nucleus and hyphal tip. Δ Fgcot 1 and Δ Fgmob 2 exhibited serious defects in hyphal growth, polarity, fungal development and cell wall integrity as well as reduced virulence in planta . In contrast, lipid droplet accumulation was significantly increased in these two mutants. Phosphorylation of FgCot1 at two highly conserved residues (S462 and T630) as well as five new sites synergistically contributed its role in various cellular processes. In addition, non‐synonymous mutations in two MAPK (mitogen‐activated protein kinase) proteins, FgSte11 and FgGpmk1, partially rescued the growth defect of Δ Fgmob2 , indicating a functional link between the FgCot1–Mob2 complex and the FgGpmk1 signalling pathway in regulating filamentous fungal growth. These results indicated that the FgCot1–Mob2 complex is critical for polarity, fungal development, cell wall organization, lipid metabolism and virulence in F. graminearum .

Nocardioides acrostichi sp. nov., a novel endophytic actinobacterium isolated from leaf of Acrostichum aureum - Xiao-Hui Chen; Fei Li; Fei-Na Li; Ming-Sheng Chen; Xiao-Rui Yan; Zi-Bang He; Shun-Lian Li; You-Lang Wu; Li Tuo (Antonie van Leeuwenhoek, 2021)

Chronic stress promotes acute myeloid leukemia progression through HMGB1/NLRP3/IL-1β signaling pathway - Na Liu; Yifan Wu; Xin Wen; Peng Li; Fei Lu; Hong Shang (Journal of Molecular Medicine, 2021)

Unconfined Compressive Properties of Fiber-Stabilized Coastal Cement Clay Subjected to Freeze–Thaw Cycles - Na Li; Yalan Zhu; Fang Zhang; Sin Mei Lim; Wangyi Wu; Wei Wang (Journal of Marine Science and Engineering, 2021)
This study aimed to investigate the feasibility of using polypropylene fiber-cement-stabilized coastal clay as base-course material or foundation material for city sustainable development by assessing its mechanical performance. The influence of the number of freeze–thaw cycles and curing ages on the mechanical properties of ordinary cemented clay (OCC) and polypropylene fiber-cemented clay (PCC) was investigated by using unconfined compressive test. The experimental results show that the addition of fiber with 1% content can increase the strength as well as the ductility of cemented clay by 12.5% and 15.6%, respectively. The strength of PCC and OCC at 22d age was 1.5 times than at 7d age. Under differently timed freeze–thaw cycles, the mechanical performance of PCC is improved, and, better than that, OCC improves by 11.8% in strength, 16.5% in strain and by 5% in degree of damage, indicating that fiber can improve the freeze–thaw resistance of cemented clay. The frost resistance of PCC and OCC increases with the increase in curing age. Finally, the variation of strength of OCC was explained through the change of micro-structure while the strength enhancing mechanism of polypropylene fiber for cemented clay was also revealed.

Resazurin as an indicator of reducing capacity for analyzing the physiologic status of deep-sea bacterium Photobacterium phosphoreum ANT-2200 - Jie Dai; Hongzhi Tang; Xuegong Li; Claire-Lise Santini; Wenpeng Cui; Na Liu; Xiaoqing Qi; Xuehua Cui; Alain Grossi; Philippe Notareschi; Wei-Jia Zhang; Long-Fei Wu (Journal of Oceanology and Limnology, 2021)

Correction to: Reduced nNOS activity is responsible for impaired fatty acid–dependent mitochondrial oxygen consumption in atrial myocardium from hypertensive rat - Yu Na Wu; Chun Li Jin; Ji Hyun Jang; Zai Hao Zhao; Sung Joon Kim; Yin Hua Zhang (Pflügers Archiv - European Journal of Physiology, 2020)

Reduced nNOS activity is responsible for impaired fatty acid–dependent mitochondrial oxygen consumption in atrial myocardium from hypertensive rat - Yu Na Wu; Chun Li Jin; Ji Hyun Jang; Zai Hao Zhao; Sung Joon Kim; Yin Hua Zhang (Pflügers Archiv - European Journal of Physiology, 2020)

Effects of arbuscular mycorrhizal fungi on redox homeostasis of rice under Cd stress - Hui Li; Xun Wen Chen; Li Wu; Na Luo; Wei Xiong Huang; Ce Hui Mo; Yan Wen Li; Lei Xiang; Hai Ming Zhao; Quan Ying Cai; Ming Hung Wong (Plant and Soil, 2020)

Screening for natural inhibitors of human topoisomerases from medicinal plants with bio-affinity ultrafiltration and LC–MS - Minxia Fan; Guilin Chen; Baoqing Sun; Jianlin Wu; Na Li; Satyajit D. Sarker; Lutfun Nahar; Mingquan Guo (Phytochemistry Reviews, 2020)

Prenatal diagnosis of 22q11.2 copy number abnormalities in fetuses via single nucleotide polymorphism array - Meiying Cai; Na Lin; Linjuan Su; Xiaoqing Wu; Xiaorui Xie; Ying Li; Yuan Lin; Hailong Huang; Liangpu Xu (Molecular Biology Reports, 2020)
The q11.2 region on chromosome 22 contains numerous low-copy repeats that lead to deleted or duplicated regions in the chromosome, thereby resulting in different syndromes characterized by intellectual disabilities or congenital anomalies. The association between patient phenotypes and 22q11.2 copy number abnormalities has been previously described in postnatal cases; however, these features have not been systematically evaluated in prenatal cases because of limitations in phenotypic identification in prenatal testing. In this study, we investigated the detection rate of 22q11.2 copy number abnormalities in 2500 fetuses using single nucleotide polymorphism (SNP) array and determined the common abnormal ultrasound findings in fetuses carrying the 22q11.2 copy number abnormalities. The 22q11.2 copy number abnormalities were identified in 13 fetuses with cardiovascular malformations (6/13), kidney malformations (3/13), isolated ultrasound markers (3/13), or high-risk Down syndrome based on maternal serum screening (1/13). Approximately 0.5% (13/2500) of the fetuses harbored 22q11.2 copy number abnormalities. The most frequent ultrasound findings in fetuses with these abnormalities were cardiovascular malformations, followed by kidney malformations and isolated ultrasound markers. Prenatal diagnosis of these genetic abnormalities allows for the delineation of differential diagnoses, characterization of a wide spectrum of associated malformations, and determination of associations that exist between prenatal diagnosis and obstetrical outcomes.

Visual motion perception improvements following direct current stimulation over V5 are dependent on initial performance - Di Wu; Chenxi Li; Na Liu; Pengbo Xu; Wei Xiao (Experimental Brain Research, 2020)

Correction to: CCR2 and CCR5 promote diclofenac-induced hepatotoxicity in mice - Zhanke He; Guoquan Wei; Na Li; Mengwei Niu; Shenhai Gong; Guangyan Wu; Teng Wang; Yong Jiang; Peng Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Production, Identification and Characterization of Erianthus rockii × Narenga porphyrocoma Intergeneric Hybrids as a New Germplasm for Sugarcane Breeding and Genetic Research - Hailong Chang; Qinnan Wang; Yongsheng Qiu; Yuanxia Qin; Xueting Li; Qingdan Wu; Weiping He; Yuqiang Guo; Wei Zhang; Junlv Chen; Na Fang (Sugar Tech, 2020)

Scutellarin Exerts Anti-Inflammatory Effects in Activated Microglia/Brain Macrophage in Cerebral Ischemia and in Activated BV-2 Microglia Through Regulation of MAPKs Signaling Pathway - Hao-Lun Chen; Wen-Ji Jia; Hong-E Li; Hong Han; Fan Li; Xiao-Li-Na Zhang; Juan-Juan Li; Yun Yuan; Chun-Yun Wu (NeuroMolecular Medicine, 2020)

Antagonistic regulation of axillary bud outgrowth by the BRANCHED genes in tobacco - Na Ding; Qiulin Qin; Xia Wu; Robert Miller; David Zaitlin; Dandan Li; Shengming Yang (Plant Molecular Biology, 2020)

Cell membrane damage induced by continuous stress of artemisinin sustained-release microspheres (ASMs) on Microcystis aeruginosa at different physiological stages - Lixiao Ni; Feifei Yue; Jianhua Zhang; Shiyi Rong; Xuanyu Liu; Yifei Wang; Peifang Wang; Danye Li; Na Wang; Hanqi Wu; Shiyin Li (Environmental Science and Pollution Research, 2020)

Development of polyclonal-antibody-coated immunomagnetic beads for separation and detection of koi herpesvirus in large-volume samples - Min Zhang; Yingying Li; Hongli Jing; Na Wang; Shaoqiang Wu; Qing Wang; Xiangmei Lin (Archives of Virology, 2020)

Membrane proteomic analysis reveals the intestinal development is deteriorated by intrauterine growth restriction in piglets - Shimeng Huang; Cong Liu; Na Li; Zhenhua Wu; Tiantian Li; Dandan Han; Zhen Li; Jiangchao Zhao; Junjun Wang (Functional & Integrative Genomics, 2020)

Characteristics and temporal variations of organic and elemental carbon aerosols in PM1 in Changchun, Northeast China - Na Li; Xin Wei; Weizheng Han; Siyue Sun; Jinghui Wu (Environmental Science and Pollution Research, 2020)

Molecular characterization of a novel botoulivirus from the phytopathogenic fungus Sclerotinia minor - Na Liang; Dan Yang; Mingde Wu; Jing Zhang; Guoqing Li; Long Yang (Archives of Virology, 2020)

Chemical constituents from Ginkgo biloba leaves and their cytotoxicity activity - Penghua Shu; Mengyuan Sun; Junping Li; Lingxiang Zhang; Haichang Xu; Yueyue Lou; Zhiyu Ju; Xialan Wei; Wenming Wu; Na Sun (Journal of Natural Medicines, 2020)

Hirsutella sinensis inhibits NLRP3 inflammasome activation to block aristolochic acid-induced renal tubular epithelial cell transdifferentiation - Min Yu; Yu-lin Man; Meng-hua Chen; Li-hua Wu; Yi Zhou; Xiao-ling Zhou; Na Chen; Rui Ma; Li-na Sun (Human Cell, 2020)

Stress-dependent anisotropy index of strength and deformability of jointed rock mass: insights from a numerical study - Na Wu; Zheng-zhao Liang; Ying-chun Li; Hong Li; Wan-run Li; Mei-li Zhang (Bulletin of Engineering Geology and the Environment, 2019)

Characterization of the complete mitochondrial genome of the mole salamander Ambystoma talpoideum (Caudata: Ambystomatidae) - Zhuo-Lu Ren; Na-Na Yao; Li Liu; Yi Wu; Zeng-Qiang Qian (Conservation Genetics Resources, 2019)

Numerical Study on Anisotropy of the Representative Elementary Volume of Strength and Deformability of Jointed Rock Masses - Zhengzhao Liang; Na Wu; Yingchun Li; Hong Li; Wanrun Li (Rock Mechanics and Rock Engineering, 2019)

Fn14 Participates in Neuropathic Pain Through NF-κB Pathway in Primary Sensory Neurons - Li-Na Huang; Yun Zou; Shao-Gen Wu; Hong-Hong Zhang; Qing-Xiang Mao; Jin-Bao Li; Yuan-Xiang Tao (Molecular Neurobiology, 2019)

Increased CXCL13 and CXCR5 in Anterior Cingulate Cortex Contributes to Neuropathic Pain-Related Conditioned Place Aversion - Xiao-Bo Wu; Li-Na He; Bao-Chun Jiang; Xue Wang; Ying Lu; Yong-Jing Gao (Neuroscience Bulletin, 2019)

The evolution of the spatial-temporal patterns of global energy security since the 1990s - Qiang Wang; Linglin Xu; Na Li; Xue Du; Shidai Wu; Lanlan Tian; Chenlu Wu (Journal of Geographical Sciences, 2019)

Microenvironment and microbial community in the rhizosphere of dioecious Populus cathayana at Chaka Salt Lake - Na Wu; Zhen Li; Fei Wu; Ming Tang (Journal of Soils and Sediments, 2019)

Nivolumab-induced Thyroid Dysfunctions in Patients with Previously Treated Non-small Cell Lung Cancer - Xinyong Zhang; Yuhua Wu; Jialin Lv; Xi Li; Li Ma; Jingying Nong; Hui Zhang; Na Qin; Quan Zhang; Guangli Shi; Xinjie Yang; Jinghui Wang; et al. (Interdisciplinary Sciences: Computational Life Sciences, 2019)

OsCDC48/48E complex is required for plant survival in rice (Oryza sativa L.) - Lei Shi; Xiao-bo Zhang; Yong-feng Shi; Xia Xu; Yuqing He; Guosheng Shao; Qi-na Huang; Jian-li Wu (Plant Molecular Biology, 2019)

The Toxicological Effects of Mercury Exposure in Marine Fish - Na Zheng; Sujing Wang; Wu Dong; Xiuyi Hua; Yunyang Li; Xue Song; Qingwen Chu; Shengnan Hou; Yang Li (Bulletin of Environmental Contamination and Toxicology, 2019)

Transcriptome analysis of 1- and 3-year-old Panax notoginseng roots and functional characterization of saponin biosynthetic genes DS and CYP716A47-like - Jian Li; Lan Ma; Shuting Zhang; Cailian Zuo; Na Song; Shusheng Zhu; Jinsong Wu (Planta, 2019)

CCR2 and CCR5 promote diclofenac-induced hepatotoxicity in mice - Zhanke He; Guoquan Wei; Na Li; Mengwei Niu; Shenhai Gong; Guangyan Wu; Teng Wang; Yong Jiang; Peng Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Complete genome analysis of a novel phage GW1 lysing Cronobacter - Haiyan Zeng; Wenjing He; Chengsi Li; Jumei Zhang; Na Ling; Yu Ding; Liang Xue; Moutong Chen; Haoming Wu; Qingping Wu (Archives of Virology, 2019)

sEMG Based Gait Phase Recognition for Children with Spastic Cerebral Palsy - Peng-na Wei; Rongfu Xie; Rongnian Tang; Chuang Li; Janis Kim; Ming Wu (Annals of Biomedical Engineering, 2019)

Synergistic degradation of trans-ferulic acid in aqueous solution by dielectric barrier discharge plasma combined with ozone - Jingyu Ren; Nan Jiang; Jie Li; Kefeng Shang; Na Lu; Yan Wu (Environmental Science and Pollution Research, 2018)

Sex Differences in Neuropathology and Cognitive Behavior in APP/PS1/tau Triple-Transgenic Mouse Model of Alzheimer’s Disease - Jun-Ting Yang; Zhao-Jun Wang; Hong-Yan Cai; Li Yuan; Meng-Ming Hu; Mei-Na Wu; Jin-Shun Qi (Neuroscience Bulletin, 2018)

Expression of BC1 Impairs Spatial Learning and Memory in Alzheimer’s Disease Via APP Translation - Tongmei Zhang; Pei Pang; Zemin Fang; Yu Guo; Hao Li; Xinyan Li; Tian Tian; Xin Yang; Wenting Chen; Shu Shu; Na Tang; Jianhua Wu; et al. (Molecular Neurobiology, 2018)

Description of a new species of Triplophysa (Teleostei: Nemacheilidae) from Guizhou Province, China - Wei‐Jun Wu; An‐You He; Jun‐Xing Yang; Li‐Na Du (Journal of Fish Biology, 2018)
A new cave‐dwelling fish species Triplophysa guizhouensis is described based on specimens collected from Guizhou, China, in a subterranean system interconnected with the Hongshui River drainage. The species can be distinguished from its congeners by a combination of characters: eyes present; caudal fin with 14 branched rays; inner gill rakers of first gill arch 8–10; posterior chamber of air bladder developed; and body posterior of dorsal fin scaled. A key to species of Triplophysa in the Pearl River basin is provided.

Conflicting meal recommendations for oral oncology drugs: pose risks to patient care? - Guo Yu; Dan-Na Wu; Yan Gong; Guo-Fu Li; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2018)

Both widespread PEP‐CTERM proteins and exopolysaccharides are required for floc formation of Zoogloea resiniphila and other activated sludge bacteria - Na Gao; Ming Xia; Jingcheng Dai; Dianzhen Yu; Weixing An; Shuyang Li; Shuangyuan Liu; Penghui He; Liping Zhang; Zhenbin Wu; Xuezhi Bi; Shouwen Chen; et al. (Environmental Microbiology, 2018)
Summary Bacterial floc formation plays a central role in the activated sludge (AS) process, which has been widely utilized for sewage and wastewater treatment. The formation of AS flocs has long been known to require exopolysaccharide biosynthesis. This study demonstrates an additional requirement for a PEP‐CTERM protein in Zoogloea resiniphila , a dominant AS bacterium harboring a large exopolysaccharide biosynthesis gene cluster. Two members of a wide‐spread family of high copy number‐per‐genome PEP‐CTERM genes, transcriptionally regulated by the RpoN sigma factor and accessory PrsK‐PrsR two‐component system and at least one of these, pepA , must be expressed for Zoogloea to build the floc structures that allow gravitational sludge settling and recycling. Without PrsK or PrsR, Zoogloea cells were planktonic rather than flocculated and secreted exopolysaccharides were released into the growth broth in soluble form. Overexpression of PepA could circumvent the requirement of rpoN , prsK and prsR for the floc‐forming phenotype by fixing the exopolysaccharides to bacterial cells. However, overexpression of PepA, which underwent post‐translational modifications, could not rescue the long‐rod morphology of the rpoN mutant. Consistently, PEP‐CTERM genes and exopolysaccharide biosynthesis gene cluster are present in the genome of the floc‐forming Nitrospira comammox and Mitsuaria strain as well as many other AS bacteria.

A new pair of enantiomeric lignans from the fruits of Morinda citrifolia and their absolute configuration - Wen-Jian Liu; Yue-Juan Chen; Dan-Na Chen; Ya-Ping Wu; Yu-Jie Gao; Jing Li; Wen-Jun Zhong; Lin Jiang (Natural Product Research, 2018)

Spatial and temporal variation of the urban impervious surface and its driving forces in the central city of Harbin - Miao Li; Shuying Zang; Changshan Wu; Xiaodong Na (Journal of Geographical Sciences, 2018)

Establishment and characterization of a kidney cell line from kelp grouper Epinephelus moara - Xiao-Feng Liu; Ya-Hong Wu; Shi-Na Wei; Na Wang; Peng-Fei Li; Yang-Zhen Li; Nian-Wei Zhang; Qi-Wei Qin; Song-Lin Chen (Fish Physiology and Biochemistry, 2018)

Available forms of nutrients and heavy metals control the distribution of microbial phospholipid fatty acids in sediments of the Three Gorges Reservoir, China - Hongyang Sun; Yanhong Wu; Haijian Bing; Jun Zhou; Na Li (Environmental Science and Pollution Research, 2018)

Viral metagenomics of six bat species in close contact with humans in southern China - Xue-yan Zheng; Min Qiu; Wei-jie Guan; Jin-ming Li; Shao-wei Chen; Ming-ji Cheng; Shu-ting Huo; Zhong Chen; Yi Wu; Li-na Jiang; Qing Chen (Archives of Virology, 2018)

An investigation of the health effects caused by exposure to arsenic from drinking water and coal combustion: arsenic exposure and metabolism - Binggan Wei; Jiangping Yu; Chang Kong; Hairong Li; Linsheng Yang; Zhiwei Guo; Na Cui; Yajuan Xia; Kegong Wu (Environmental Science and Pollution Research, 2017)

Kinetics of Antioxidant-Producing Maillard Reaction in the Mixture of Ribose and Sea Cucumber ( Stichopus japonicus ) Gut Hydrolysates - Jia-Run Han; Zhi-Mo Zhu; Hai-Tao Wu; Na Sun; Yue Tang; Cui-Ping Yu; Chen-Chen Zhao; Zheng-Yu Zhang; Ao-Ting Li; Jia-Nan Yan (Journal of Aquatic Food Product Technology, 2017)

Negligible effect of eNOS palmitoylation on fatty acid regulation of contraction in ventricular myocytes from healthy and hypertensive rats - Chun Li Jin; Yu Na Wu; Ji Hyun Jang; Zai Hao Zhao; Goo Taeg Oh; Sung Joon Kim; Yin Hua Zhang (Pflügers Archiv - European Journal of Physiology, 2017)

Expression of Iron Transporters and Pathological Hallmarks of Parkinson’s and Alzheimer’s Diseases in the Brain of Young, Adult, and Aged Rats - Li-Na Lu; Zhong-Ming Qian; Ka-Chun Wu; Wing-Ho Yung; Ya Ke (Molecular Neurobiology, 2017)

Ion Channel Genes and Epilepsy: Functional Alteration, Pathogenic Potential, and Mechanism of Epilepsy - Feng Wei; Li-Min Yan; Tao Su; Na He; Zhi-Jian Lin; Jie Wang; Yi-Wu Shi; Yong-Hong Yi; Wei-Ping Liao (Neuroscience Bulletin, 2017)

Resveratrol Inhibits Diabetic-Induced Müller Cells Apoptosis through MicroRNA-29b/Specificity Protein 1 Pathway - Kaihong Zeng; Yuan Wang; Na Yang; Duozi Wang; Suping Li; Jian Ming; Jing Wang; Xuemei Yu; Yi Song; Xue Zhou; Bo Deng; Xiaona Wu; et al. (Molecular Neurobiology, 2017)

Biosynthesis of staphylococcal enterotoxin A by genetic engineering technology and determination of staphylococcal enterotoxin A in water by HPLC-ESI-TOF - Hong-na Li; Fei Yuan; Yun-jing Luo; Jian-feng Wang; Chuan-bin Zhang; Wei-e Zhou; Zhi-qin Ren; Wen-jie Wu; Feng Zhang (Environmental Science and Pollution Research, 2017)

Developing the science product algorithm testbed for Chinese next-generation geostationary meteorological satellites: Fengyun-4 series - Min Min; Chunqiang Wu; Chuan Li; Hui Liu; Na Xu; Xiao Wu; Lin Chen; Fu Wang; Fenglin Sun; Danyu Qin; Xi Wang; Bo Li; et al. (Journal of Meteorological Research, 2017)

Isolation of Viable but Non-culturable Bacteria from Printing and Dyeing Wastewater Bioreactor Based on Resuscitation Promoting Factor - Yi Jin; Guojuan Gan; Xiaoyun Yu; Dongdong Wu; Li Zhang; Na Yang; Jiadan Hu; Zhiheng Liu; Lixin Zhang; Huachang Hong; Xiaoqing Yan; Yan Liang; et al. (Current Microbiology, 2017)

Transcriptional sequencing and analysis of major genes involved in the adventitious root formation of mango cotyledon segments - Yun-He Li; Hong-Na Zhang; Qing-Song Wu; Gloria K. Muday (Planta, 2017)

The species of Lentaria (Gomphales, Basidiomycota) from China based on morphological and molecular evidence - Li-Na Liu; Ling Wu; Zuo-Hong Chen; Tolgor Bau; Ping Zhang (Mycological Progress, 2017)

A Point Mutation in SCN1A 5′ Genomic Region Decreases the Promoter Activity and Is Associated with Mild Epilepsy and Seizure Aggravation Induced by Antiepileptic Drug - Qu-Wen Gao; Li-Dong Hua; Jie Wang; Cui-Xia Fan; Wei-Yi Deng; Bin Li; Wen-Jun Bian; Chuan-Xing Shao; Na He; Peng Zhou; Wei-Ping Liao; Yi-Wu Shi (Molecular Neurobiology, 2017)

A comparative study on the landslide susceptibility mapping using logistic regression and statistical index models - Zhiyong Wu; Yanli Wu; Yitian Yang; Fuwei Chen; Na Zhang; Yutian Ke; Wenping Li (Arabian Journal of Geosciences, 2017)

Post Plasma-Catalysis of Low Concentration VOC Over Alumina-Supported Silver Catalysts in a Surface/Packed-Bed Hybrid Discharge Reactor - Nan Jiang; Cheng Qiu; Lianjie Guo; Kefeng Shang; Na Lu; Jie Li; Yan Wu (Water, Air, & Soil Pollution, 2017)

Effect of Partial Shading Treatments on Anthocyanin Synthesis in the Hypocotyls of Soybean Sprouts Under UV-A irradiation - Nana Su; Qi Wu; Nannan Qi; Yuanyuan Liu; Na Li; Jin Cui (Journal of Plant Growth Regulation, 2017)

Activation of group I metabotropic glutamate receptors regulates the excitability of rat retinal ganglion cells by suppressing Kir and I h - Qian Li; Peng Cui; Yanying Miao; Feng Gao; Xue-Yan Li; Wen-Jing Qian; Shu-Xia Jiang; Na Wu; Xing-Huai Sun; Zhongfeng Wang (Brain Structure and Function, 2017)

Arsenic methylation and skin lesions in migrant and native adult women with chronic exposure to arsenic from drinking groundwater - Binggan Wei; Jiangping Yu; Linsheng Yang; Hairong Li; Yuanqing Chai; Yajuan Xia; Kegong Wu; Jianwei Gao; Zhiwei Guo; Na Cui (Environmental Geochemistry and Health, 2017)

Historical introduction, geographical distribution, and biological characteristics of alien plants in China - Chao Chen; Qing-Hai Wang; Ju-Ying Wu; Ding Huang; Wei-Hua Zhang; Na Zhao; Xue-Feng Li; Li-Xue Wang (Biodiversity and Conservation, 2017)

A new piperidine alkaloid from the leaves of Microcos paniculata L. - Gang Zhang; Na Zhang; Li Xu; Hong-Tan Wu; Dan Chen; Qi-Huang Lin; Lian-Zhong Luo (Natural Product Research, 2017)

Improved salt tolerance of medicinal plant Codonopsis pilosula by Bacillus amyloliquefaciens GB03 - Qing-Qing Han; Yong-Na Wu; Hui-Juan Gao; Rui Xu; Paul W. Paré; Huazhong Shi; Qi Zhao; Hui-Ru Li; Sardar Ali Khan; Yin-Quan Wang; Suo-Min Wang; Jin-Lin Zhang (Acta Physiologiae Plantarum, 2017)

Identification of russet-associated microRNAs in the exocarp of a Dangshansuli pear mutant (Pyrus bretschneideri Rehd.) by high-throughput sequencing - Wei Heng; Bing Jia; Hai-na Huang; Jin-yu Yang; Zi-teng Wang; Pu Liu; Li Liu; Zhen-feng Ye; Li-wu Zhu (Tree Genetics & Genomes, 2016)

Heavy metals in the riverbed surface sediment of the Yellow River, China - Qingyu Guan; Ao Cai; Feifei Wang; Lei Wang; Tao Wu; Baotian Pan; Na Song; Fuchun Li; Min Lu (Environmental Science and Pollution Research, 2016)

Fine mapping of the Rsv1-h gene in the soybean cultivar Suweon 97 that confers resistance to two Chinese strains of the soybean mosaic virus - Fang-Fang Ma; Xiao-Yi Wu; Yun-Xia Chen; Ying-Na Liu; Zhu-Qing Shao; Ping Wu; Mian Wu; Cheng-Chen Liu; Wen-Ping Wu; Jia-Yin Yang; De-Xiao Li; Jian-Qun Chen; et al. (Theoretical and Applied Genetics, 2016)

A novel diarylheptanoid-bearing sesquiterpene moiety from the rhizomes of Alpinia officinarum - Na Wei; Zhonglin Zhou; Qing Wei; Yong Wang; Jun Jiang; Junqing Zhang; Lixiang Wu; Shuiping Dai; Youbin Li (Natural Product Research, 2016)

Associations of TNF-α and IL-6 polymorphisms with osteoporosis through joint effects and interactions with LEPR gene in Taiwan: Taichung Community Health Study for Elders (TCHS-E) - Cheng-Chieh Lin; Tsai-Chung Li; Chiu-Shong Liu; Chuan-Wei Yang; Chih-Hsueh Lin; Jen-Hao Hsiao; Nai-Hsin Meng; Wen-Yuan Lin; Li-Na Liao; Chia-Ing Li; Fang-Yang Wu (Molecular Biology Reports, 2016)

Effects of yeast products on the intestinal morphology, barrier function, cytokine expression, and antioxidant system of weaned piglets - Huan-sheng Yang; Fei Wu; Li-na Long; Tie-jun Li; Xia Xiong; Peng Liao; Hong-nan Liu; Yu-long Yin (Journal of Zhejiang University-SCIENCE B, 2016)

Sirtuin-3 (SIRT3) protects pancreatic β-cells from endoplasmic reticulum (ER) stress-induced apoptosis and dysfunction - Hao-Hao Zhang; Xiao-Jun Ma; Li-Na Wu; Yan-Yan Zhao; Peng-Yu Zhang; Ying-Hui Zhang; Ming-Wei Shao; Fei Liu; Fei Li; Gui-Jun Qin (Molecular and Cellular Biochemistry, 2016)

Prognostic significance of FLT3-ITD in pediatric acute myeloid leukemia: a meta-analysis of cohort studies - Xiaoli Wu; Xuefeng Feng; Xiaoqing Zhao; Futian Ma; Na Liu; Hongming Guo; Chaonan Li; Huan Du; Baoxi Zhang (Molecular and Cellular Biochemistry, 2016)

The effect of immunosuppressive drug cyclosporine A on myeloid-derived suppressor cells in transplanted mice - Chenlu Han; Tingting Wu; Ning Na; Yang Zhao; Weiguo Li; Yong Zhao (Inflammation Research, 2016)

[Gly14]-Humanin Protects Against Amyloid β Peptide-Induced Impairment of Spatial Learning and Memory in Rats - Li Yuan; Xiao-Jie Liu; Wei-Na Han; Qing-Shan Li; Zhao-Jun Wang; Mei-Na Wu; Wei Yang; Jin-Shun Qi (Neuroscience Bulletin, 2016)

TNFα-induced M-MDSCs promote transplant immune tolerance via nitric oxide - Fan Yang; Yang Li; Tingting Wu; Ning Na; Yang Zhao; Weiguo Li; Chenlu Han; Lianfeng Zhang; Jun Lu; Yong Zhao (Journal of Molecular Medicine, 2016)

Trade‐offs and evolution of thermal adaptation in the Irish potato famine pathogen Phytophthora infestans - Li‐Na Yang; Wen Zhu; E‐Jiao Wu; Ce Yang; Peter H. Thrall; Jeremy J. Burdon; Li‐Ping Jin; Li‐Ping Shang; Jiasui Zhan (Molecular Ecology, 2016)
Temperature is one of the most important environmental parameters with crucial impacts on nearly all biological processes. Due to anthropogenic activity, average air temperatures are expected to increase by a few degrees in coming decades, accompanied by an increased occurrence of extreme temperature events. Such global trends are likely to have various major impacts on human society through their influence on natural ecosystems, food production and biotic interactions, including diseases. In this study, we used a combination of statistical genetics, experimental evolution and common garden experiments to investigate the evolutionary potential for thermal adaptation in the potato late blight pathogen, Phytophthora infestans , and infer its likely response to changing temperatures. We found a trade‐off associated with thermal adaptation to heterogeneous environments in P. infestans, with the degree of the trade‐off peaking approximately at the pathogen's optimum growth temperature. A genetic trade‐off in thermal adaptation was also evidenced by the negative association between a strain's growth rate and its thermal range for growth, and warm climates selecting for a low pathogen growth rate. We also found a mirror effect of phenotypic plasticity and genetic adaptation on growth rate. At below the optimum, phenotypic plasticity enhances pathogen's growth rate but nature selects for slower growing genotypes when temperature increases. At above the optimum, phenotypic plasticity reduces pathogen's growth rate but natural selection favours for faster growing genotypes when temperature increases further. We conclude from these findings that the growth rate of P. infestans will only be marginally affected by global warming.

Isolation, identification and genomic characterization of the Asian lineage Zika virus imported to China - Yong-Qiang Deng; Hui Zhao; Xiao-Feng Li; Na-Na Zhang; Zhong-Yu Liu; Tao Jiang; Da-Yong Gu; Lei Shi; Jian-An He; Hong-Jiang Wang; Zhao-Zeng Sun; Qing Ye; et al. (Science China Life Sciences, 2016)

Infralimbic Endothelin1 Is Critical for the Modulation of Anxiety-Like Behaviors - Lin-Lin Bi; Ming Chen; Lei Pei; Shu Shu; Hui-Juan Jin; Hong-Lin Yan; Na Wei; Shan Wang; Xin Yang; Huan-Huan Yan; Meng-meng Xu; Cheng-Ye Yao; et al. (Molecular Neurobiology, 2016)

Arsenic Metabolites and Methylation Capacity Among Individuals Living in a Rural Area with Endemic Arseniasis in Inner Mongolia, China - Binggan Wei; Jiangping Yu; Hairong Li; Linsheng Yang; Yajuan Xia; Kegong Wu; Jianwei Gao; Zhiwei Guo; Na Cui (Biological Trace Element Research, 2016)

Eimeria tenella: a novel dsRNA virus in E. tenella and its complete genome sequence analysis - Bin Wu; Xichen Zhang; Pengtao Gong; Mingying Li; He Ding; Caiyan Xin; Na Zhao; Jianhua Li (Virus Genes, 2016)

Impact of industrialization on water protection in the Huai River Basin within Shandong Province, China - Na Li; Yanan Wei; Lachun Wang; Chunfen Zeng; Xiaoxue Ma; Hao Wu (Natural Hazards, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Alteration of cytochrome P450 1 regulation and HSP 70 level in brain of juvenile common carp (Cyprinus carpio) after chronic exposure to tributyltin - Zhi-Hua Li; Li-Qiao Zhong; Yan-Hua Wu; Wei-Na Mu (Fish Physiology and Biochemistry, 2016)

High prevalence and diversity of viruses of the subfamily Gammaherpesvirinae, family Herpesviridae, in fecal specimens from bats of different species in southern China - Xue-yan Zheng; Min Qiu; Shao-wei Chen; Jian-peng Xiao; Li-zhen Ma; Shan Liu; Jun-hua Zhou; Qiong-hua Zhang; Xing Li; Zhong Chen; Yi Wu; Hui-fang Chen; et al. (Archives of Virology, 2016)

Radix ranunculus temate saponins induces apoptosis via the death receptor and mitochondrial pathways in SGC-7901 cells - Mao-lin Li; Han-min Gu; Hong-ya Hang; Yao-li Jiang; Jiao Jiang; Qian-na Gu; Wen-yan Wu (Molecular & Cellular Toxicology, 2015)

Mapping forested wetlands in the Great Zhan River Basin through integrating optical, radar, and topographical data classification techniques - X. D. Na; S. Y. Zang; C. S. Wu; W. L. Li (Environmental Monitoring and Assessment, 2015)

Reproductive management through integration of PGD and MPS-based noninvasive prenatal screening/diagnosis for a family with GJB2-associated hearing impairment - WenPing Xiong; DaYong Wang; Yuan Gao; Ya Gao; HongYang Wang; Jing Guan; Lan Lan; JunHao Yan; Liang Zong; Yuan Yuan; Wei Dong; SeXin Huang; et al. (Science China Life Sciences, 2015)

Characterization of important odorants in four steamed Coilia ectenes from China by gas chromatography–mass spectrometry–olfactometry - Lin-min Zhao; Wei Wu; Ning-ping Tao; Yu-qi Li; Na Wu; Xiao Qin (Fisheries Science, 2015)

Geographic and genetic identification of RppS, a novel locus conferring broad resistance to southern corn rust disease in China - Xiaojun Wu; Na Li; Panfeng Zhao; Yan He; Shoucai Wang (Euphytica, 2015)

Isolation of differentially expressed sex genes in garden asparagus using suppression subtractive hybridization - Chuan-liang Deng; Ning-na Wang; Shu-fen Li; Tian-yu Dong; Xin-peng Zhao; Shao-jing Wang; Wu-jun Gao; Long-dou Lu (Journal of Plant Research, 2015)

Influence of arbuscular mycorrhiza on photosynthesis and water status of Populus cathayana Rehder males and females under salt stress - Na Wu; Zhen Li; Hongguang Liu; Ming Tang (Acta Physiologiae Plantarum, 2015)

Potential probiotic attributes of a new strain of Bacillus coagulans CGMCC 9951 isolated from healthy piglet feces - Shao-Bin Gu; Li-Na Zhao; Ying Wu; Shi-Chang Li; Jian-Rui Sun; Jing-Fang Huang; Dan-Dan Li (World Journal of Microbiology and Biotechnology, 2015)

Within-litter variation in birth weight: impact of nutritional status in the sow - Tao-lin Yuan; Yu-hua Zhu; Meng Shi; Tian-tian Li; Na Li; Guo-yao Wu; Fuller W. Bazer; Jian-jun Zang; Feng-lai Wang; Jun-jun Wang (Journal of Zhejiang University-SCIENCE B, 2015)

Dissipation and Degradation Dynamics of Thifluzamide in Rice Field - Li Na Wei; Ping Wu; Fu Rong Wang; Hong Yang (Water, Air, & Soil Pollution, 2015)

Design and applications of bifunctional cinnamide derivatives as potential antimycobacterial agents with few hepatotoxic effects - Zheng-Rong Wu; De-Juan Zhi; Li-Fang Zheng; Jian-Ying Li; Yang Li; Qing-Jian Xie; Na Feng; Yan-Fang Bao; Qi-Yu Gao; Ying Song; Hong-Yu Li (Medicinal Chemistry Research, 2015)

Lipopolysaccharides Upregulate Hepcidin in Neuron via Microglia and the IL-6/STAT3 Signaling Pathway - Zhong-Ming Qian; Xuan He; Tuo Liang; Ka-Chun Wu; Yik-Chun Yan; Li-Na Lu; Guang Yang; Qian Qian Luo; Wing-Ho Yung; Ya Ke (Molecular Neurobiology, 2014)

Expression and Selection of Human Foxm1c Binding Peptides and Their Inhibitions on MCF7 Cancer Cells - Jian Cui; Jiaming Huang; Tailin Guo; Fang Wu; Zhijuan Liang; Lili Xiong; Tingting Huang; Li Zeng; Na Liu; Canquan Mao (International Journal of Peptide Research and Therapeutics, 2014)

Involvement of calcium-sensing receptors in hypoxia-induced vascular remodeling and pulmonary hypertension by promoting phenotypic modulation of small pulmonary arteries - Xue Peng; Hong-Xia Li; Hong-Jiang Shao; Guang-Wei Li; Jian Sun; Yu-Hui Xi; Hong-Zhu Li; Xin-Yan Wang; Li-Na Wang; Shu-Zhi Bai; Wei-Hua Zhang; Li Zhang; et al. (Molecular and Cellular Biochemistry, 2014)

Essential oil from Zanthoxylum bungeanum Maxim. and its main components used as transdermal penetration enhancers: a comparative study - Yi Lan; Hui Li; Yan-yan Chen; Ye-wen Zhang; Na Liu; Qing Zhang; Qing Wu (Journal of Zhejiang University-SCIENCE B, 2014)

Simultaneous determination by UPLC-MS/MS of seven bioactive compounds in rat plasma after oral administration of Ginkgo biloba tablets: application to a pharmacokinetic study - Wen-ping Wang; Na Liu; Qian Kang; Pei-pei Du; Yi Lan; Bo-chen Zhao; Yan-yan Chen; Qing Zhang; Hui Li; Ye-wen Zhang; Qing Wu (Journal of Zhejiang University-SCIENCE B, 2014)

A novel deletion mutation of the ADAR1 gene in a Chinese patient with dyschromatosis symmetrica hereditaria - WEI-WEI LI; QIU-YUE WU; NA LI; DE-QUAN DENG; RU-SONG ZHANG; YING-XIA CUI; XIAO-JUN LI; XIN-YI XIA (Journal of Genetics, 2014)

Forsythin inhibits lipopolysaccharide-induced inflammation by suppressing JAK-STAT and p38 MAPK signalings and ROS production - Xiaolong Pan; Xiang Cao; Na Li; Yimiao Xu; Qiuyue Wu; Jing Bai; Zhimin Yin; Lan Luo; Lei Lan (Inflammation Research, 2014)

Evaluating the Effects of Silent Discharge Plasma on Remediation of Acid Scarlet GR-Contaminated Soil - Na Lu; Jing Lou; Cui Hua Wang; Jie Li; Yan Wu (Water, Air, & Soil Pollution, 2014)

p-Synephrine suppresses lipopolysaccharide-induced acute lung injury by inhibition of the NF-κB signaling pathway - Qianchao Wu; Ruisheng Li; Lanan Wassy Soromou; Na Chen; Xue Yuan; Guoquan Sun; Beibei Li; Haihua Feng (Inflammation Research, 2014)

Runoff characteristics of the Nen River Basin and its cause - Hong-yan Li; Yu-xin Wang; Li-na Jia; Ya-nan Wu; Miao Xie (Journal of Mountain Science, 2014)

A cellular response protein induced during HSV-1 infection inhibits viral replication by interacting with ATF5 - LianQiu Wu; XueMei Zhang; YanChun Che; Ying Zhang; SongQing Tang; Yun Liao; RuiXiong Na; XiangLin Xiong; LongDing Liu; QiHan Li (Science China Life Sciences, 2013)

NBS1 rs1805794G>C polymorphism is associated with decreased risk of acute myeloid leukemia in a Chinese population - Na Li; Yanzhe Xu; Jian Zheng; Lan Jiang; Yonghe You; Hongchun Wu; Wei Li; Depei Wu; Yifeng Zhou (Molecular Biology Reports, 2013)

ATP Regulates Sodium Channel Kinetics in Pancreatic Islet Beta Cells - Na Zou; Xiao Wu; Yan-Yan Jin; Meng-Zao He; Xin-Xin Wang; Li-Da Su; Marjan Rupnik; Zhen-Yong Wu; Li Liang; Ying Shen (The Journal of Membrane Biology, 2013)

DNA polymerase beta promoter mutations affect gene transcription, translation and the sensitivity of esophageal cancer cells to cisplatin treatment - Tao Wang; Wenqiao Zang; Yunyun Ma; Min Li; Xiaoyan Xuan; Na Wang; Rui Wu; Yuebai Li; Ziming Dong; Guoqiang Zhao (Molecular Biology Reports, 2013)

Functional polymorphisms in PIN1 promoter and esophageal carcinoma susceptibility in Chinese population - Yonghe You; Jieqiong Deng; Jian Zheng; Lan Jiang; Na Li; Hongchun Wu; Wei Li; Jiachun Lu; Yifeng Zhou; Bin Ni (Molecular Biology Reports, 2013)

Spatiotemporal patterns and essential role of TNF receptor-associated factor 5 expression after rat spinal cord Injury - Weipeng Huan; Xiujie Wu; Shuangwei Zhang; Yin Zhao; Hua Xu; Na Wang; Honghui Li; Hailei Chen; Haixiang Wei; Youhua Wang (Journal of Molecular Histology, 2012)

Molecular and cytological evidences for the natural wheatgrass hybrids occurrence and origin in west China - Jian Zeng; Xing Fan; Hai-Qin Zhang; Li-Na Sha; Hou-Yang Kang; Li Zhang; Rui-Wu Yang; Chun-Bang Ding; Yong-Hong Zhou (Genes & Genomics, 2012)

Impairment of liver regeneration by the histone deacetylase inhibitor valproic acid in mice - Qi Ke; Rui-na Yang; Feng Ye; Yu-jia Wang; Qiong Wu; Li Li; Hong Bu (Journal of Zhejiang University-SCIENCE B, 2012)

Glutathione peroxidase from the white shrimp Litopenaeus vannamei: characterization and its regulation upon pH and Cd exposure - Lei Wang; Juan Wu; Wei-Na Wang; Dan-Xia Cai; Yuan Liu; An-Li Wang (Ecotoxicology, 2012)

The respiratory burst activity and expression of catalase in white shrimp, Litopenaeus vannamei, during long-term exposure to pH stress - Wei-Na Wang; Bao-Sheng Li; Jin-Jian Liu; Lei Shi; M. J. Alam; Shi-Juan Su; Juan Wu; Lei Wang; An-Li Wang (Ecotoxicology, 2012)

Enhanced Anti-Diabetic Activity of a Combination of Chromium(III) Malate Complex and Propolis and its Acute Oral Toxicity Evaluation - Xiang-Yang Wu; Fang Li; Ting Zhao; Guang-Hua Mao; Jing Li; Hong-Yuan Qu; Yue-Na Ren; Liu-Qing Yang (Biological Trace Element Research, 2012)

Genome-Wide Expression Profiling of the Response to Linezolid in Mycobacterium tuberculosis - Junchao Liang; Xudong Tang; Na Guo; Kaiyu Zhang; Aizhen Guo; Xiuping Wu; Xuelin Wang; Zhenhong Guan; Lihui Liu; Fengge Shen; Mingxun Xing; Liqiang Liu; et al. (Current Microbiology, 2012)

Phylogeny and molecular evolution of the DMC1 gene within the StH genome species in Triticeae (Poaceae) - Xiao-Li Wang; Xing Fan; Jian Zeng; Li-Na Sha; Hai-Qin Zhang; Hou-Yang Kang; Rui-Wu Yang; Li Zhang; Chun-Bang Ding; Yong-Hong Zhou (Genes & Genomics, 2012)

A miR-125b binding site polymorphism in bone morphogenetic protein membrane receptor type IB gene and prostate cancer risk in China - Ninghan Feng; Bin Xu; Jun Tao; Pengchao Li; Gong Cheng; Zhichao Min; Yuanyuan Mi; Meilin Wang; Na Tong; Jialin Tang; Zhengdong Zhang; Hongfei Wu; et al. (Molecular Biology Reports, 2012)

Global transcriptional profiles of Mycobacterium tuberculosis treated with plumbagin - Haiqing Ye; Zengshan Liu; Aizhen Guo; Junchao Liang; Na Guo; Fanli Zeng; Liqiang Liu; Lei Li; Jing Jin; Xiuping Wu; Yang Li; Mingyuan Liu; et al. (World Journal of Microbiology and Biotechnology, 2011)

Influence of temperature and medium on viability of Demodex folliculorum and Demodex brevis (Acari: Demodicidae) - Ya-E Zhao; Na Guo; Li-Ping Wu (Experimental and Applied Acarology, 2011)

Effects of MboII and BspMI polymorphisms in the gonadotropin releasing hormone receptor (GnRHR) gene on sperm quality in Holstein bulls - Wu-Cai Yang; Ke-Qiong Tang; Jun-Na Yu; Chun-Yan Zhang; Xiao-Xia Zhang; Li-Guo Yang (Molecular Biology Reports, 2011)

IL-6 −174G>C polymorphism and cancer risk: a meta-analysis involving 29,377 cases and 37,739 controls - Bin Xu; Xiao-Bing Niu; Zi-Dun Wang; Wei Cheng; Na Tong; Yuan-Yuan Mi; Zhi-Chao Min; Jun Tao; Peng-Chao Li; Wei Zhang; Hong-Fei Wu; Zheng-Dong Zhang; et al. (Molecular Biology Reports, 2011)

Microarray Analysis of the Chelerythrine-Induced Transcriptome of Mycobacterium tuberculosis - Junchao Liang; Fanli Zeng; Aizhen Guo; Liqiang Liu; Na Guo; Lei Li; Jing Jin; Xiuping Wu; Mingyuan Liu; Dan Zhao; Yang Li; Qi Jin; et al. (Current Microbiology, 2011)

An MspI polymorphism in the inhibin alpha gene and its associations with superovulation traits in Chinese Holstein cows - Ke-Qiong Tang; Shu-Jing Li; Wu-Cai Yang; Jun-Na Yu; Li Han; Xiang Li; Li-Guo Yang (Molecular Biology Reports, 2011)

Flavonoid Production Is Effectively Regulated by RNAi Interference of Two Flavone Synthase Genes from Glycine max - Yi Na Jiang; Biao Wang; Hui Li; Lu Ming Yao; Tian Long Wu (Journal of Plant Biology, 2010)

The functional expression of calcium-sensing receptor in the differentiated THP-1 cells - Yu-hui Xi; Hong-zhu Li; Wei-hua Zhang; Li-na Wang; Li Zhang; Yan Lin; Shu-zhi Bai; Hong-xia Li; Ling-yun Wu; Rui Wang; Chang-qing Xu (Molecular and Cellular Biochemistry, 2010)

Rapid generation of dendritic cell specific transgenic mice by lentiviral vectors - Jinyu Zhang; Liyun Zou; Qin Liu; Jingyi Li; Jingran Zhou; Yong Wang; Na Li; Ting Liu; Hong Wei; Min Wu; Ying Wan; Yuzhang Wu (Transgenic Research, 2009)

Rottlerin protected dopaminergic cell line from cytotoxicity of 6-hydroxydopamine by inhibiting PKCδ phosphorylation - Ying Fan; Yan-Qiao Zhang; Dian-Jun Sun; Yi-Na Zhang; Xiao-Wei Wu; Jing Li (Neuroscience Bulletin, 2009)

Phylogenetic Analysis of Leymus (Poaceae: Triticeae) Inferred from Nuclear rDNA ITS Sequences - Li-na Sha; Rui-wu Yang; Xing Fan; Xiao-li Wang; Yong-hong Zhou (Biochemical Genetics, 2008)

A human homolog of mouse Lbh gene, hLBH, expresses in heart and activates SRE and AP-1 mediated MAPK signaling pathway - Jianping Ai; Yuequn Wang; Kunrong Tan; Yun Deng; Na Luo; Wuzhou Yuan; Zequn Wang; Yongqing Li; Ying Wang; Xiaoyang Mo; Chuanbing Zhu; Zhaochu Yin; et al. (Molecular Biology Reports, 2008)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)